Multilayer film

By using a specific layer combination of linear low-density polyethylene and high-density polyethylene catalyzed by multimodal metallocene in multilayer films, the problem of contradictory performance of multilayer films in the prior art is solved, and a low seal starting temperature is achieved. Low thermal viscosity temperature and high thermal viscosity improve optical and sealing properties, and promote the recyclability of packaging materials.

CN119255909APending Publication Date: 2025-01-03BOREALIS AG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380042792.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-11
Filing Date
2023-04-06
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

While achieving high stiffness, toughness and optical properties, existing multilayer films are difficult to reduce the sealing starting temperature and thermal adhesion at the same time. The recycling of packaging materials exists, especially the recycling of composite packaging films of different materials is more challenging. .

Method used

Using a multi-layer film structure based on multimodal metallocene catalysis with linear low-density polyethylene (mLLDPE) and high-density polyethylene (HDPE) to optimize the composition of the sealing layer and surface layer through specific layer combinations and polymer ratios, improving the composition of the sealing layer and surface layer. Thermal adhesion and optical properties of the film are improved by a three-layer structure (seal layer, core layer and surface layer).

Benefits of technology

Achieved low seal starting temperature, low thermal viscosity temperature and high thermal viscosity, improve the optical performance and sealing performance of the film, especially the improvement of thermal viscosity, and also provides a single material solution to improve the ability of packaging materials. Recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151930040000131
    Figure BDA0005151930040000131
  • Figure BDA0005151930040000132
    Figure BDA0005151930040000132
  • Figure BDA0005151930040000141
    Figure BDA0005151930040000141
Patent Text Reader

Abstract

The invention relates to a multilayer film comprising at least one layer (A) as a sealing layer (SL) and a layer (B) as a surface layer, which multilayer film has beneficial heat-sealing, heat-sticking and optical properties. In particular, the invention relates to a multilayer packaging film comprising at least a sealing layer (SL) based on multimodal metallocene catalyzed LLDPE and a layer (B) based on multimodal high density polyethylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a multilayer film comprising at least one layer (A) being a sealing layer (SL), and a layer (B), the multilayer film having beneficial heat seal, hot tack and optical properties. In particular, the present invention relates to a multilayer packaging film comprising at least a sealing layer (SL) based on a specific multimodal metallocene-catalyzed LLDPE and a layer (B) based on a multimodal high density polyethylene. Background Art

[0002] Nowadays, high demands are placed on packaging materials. The properties required by the packaging industry are often contradictory. Often, materials need to have high stiffness, high toughness, excellent sealing and good optical properties at the same time. In order to achieve these different properties, pure components are rarely used, but rather combinations of different polymer components. The technician can mainly use two different approaches: (a) blending two or more polymers to form a heterogeneous structure or (b) creating a multilayer structure with different materials that provide different functions. Both methods are used in the industrial field, and the latter is even more popular because the choice of materials is more diverse and there is no need to consider the difficult technical issues of complex polymer blends. Using multilayer structures known in the art, it is already possible to produce multilayer films with good properties in the packaging industry. A typical example is the combination of two layers of polyethylene, one of which is based on a polyethylene layer with a density of about 0.918 g / cm 3 The combination consists of a sealing layer of linear low-density polyethylene (LLDPE) and a core layer of medium-density polyethylene (MDPE) or linear low-density polyethylene (LLDPE) with higher density, which improves the mechanical properties. The disadvantage of this combination is that due to the higher density of polyethylene, while achieving an acceptable stiffness / toughness balance, optical properties are sacrificed.

[0003] Furthermore, a wide variety of multilayer films have been disclosed which are intended to resolve the above-mentioned problem of an unsatisfactory balance between mechanical properties (especially stiffness and toughness) and processability.

[0004] For example, WO 2008 / 104371 discloses a multilayer film laminate comprising a multilayer film having an inner layer (A), a core layer (B) and an outer layer (C) in a given layer sequence, which is laminated to a substrate.

[0005] The inner layer (A) comprises a multimodal polyethylene composition, namely a bimodal linear low density polyethylene (LLDPE) having a density of 940 kg / m 3 or lower, a molecular weight distribution Mw / Mn of at least 8, and an MFR2 determined according to ISO 1133 (190° C. and 2.16 kg load) of 0.01 to 20 g / 10 min.

[0006] Preferably, the LLDPE comprises ethylene-1-hexene copolymer, ethylene-1-octene copolymer or ethylene-1-butene copolymer.

[0007] Layer (C) comprises LLDPE, which may be unimodal or multimodal LLDPE. In addition, the LLDPE may be znLLDPE, or the LLDPE may also be polymerized using a metallocene catalyst (mLLDPE). mLLDPE and znLLDPE are both preferred. Also preferably, layer (C) may comprise a low density polyethylene (LDPE) homopolymer or copolymer composition obtained by high pressure polymerization.

[0008] Layer (B) may comprise or consist of the same polymer composition used in layer (A) or layer (C).

[0009] Commercial grade LLDPE FB2310 or FB2230 is an example of a viable multimodal LLDPE for at least layer (A) and, if present, for optional layers, such as layer (B).

[0010] Film properties such as seal initiation temperature (SIT) or hot tack are not mentioned at all.

[0011] WO 2006 / 037603 discloses a three-layer structure, the outer layer of which comprises LLDPE, preferably unimodal LLDPE, in particular unimodal mLLDPE. The LLDPE is preferably a C2 / C6 copolymer.

[0012] One or both outer layers may contain LDPE.

[0013] It is further disclosed that a specific film may comprise a first outer layer comprising a blend of unimodal LLDPE and LDPE and a further outer layer formed of a multimodal LLDPE optionally in combination with a LDPE component.

[0014] The core layer comprises a multimodal polyethylene component having a lower molecular weight component and a higher molecular weight component, ie a multimodal LLDPE.

[0015] Thus, the multimodal PE comprises a higher molecular weight component, which preferably corresponds to an ethylene copolymer, and a lower molecular weight component, which corresponds to an ethylene homopolymer or copolymer.Such a three-layer film is particularly suitable for the production of sachets.

[0016] Film properties such as seal initiation temperature (SIT) or hot tack are not mentioned at all.

[0017] For packaging companies, it is critical to reduce the seal initiation temperature (SIT) of packaging films. From a sustainable and circular perspective, low sealing temperatures, low hot tack temperatures (HTT) and high hot tack forces (HTF) are more desirable. Lower SIT and higher HTF allow packaging lines to run faster and / or at lower temperatures, saving costs and energy.

[0018] It was therefore an object of the present invention to provide multilayer films having low SIT and HTT and a higher HTF than the multilayer films known in the prior art. Furthermore, it was an object of the present invention to provide multilayer films having improved optical properties, in particular reduced haze.

[0019] Another problem is the recycling of packaging materials after their first use. Recycling packaging films made of different materials, such as different plastics, is more challenging than recycling single-material solutions. On the other hand, it is sometimes necessary to use different materials to obtain acceptable properties, such as sealing properties and mechanical properties. Therefore, another object of the present invention is to provide a single-material solution based on polyethylene, which has good sealing properties.

[0020] The present inventors have found that a multilayer polyethylene film containing certain carefully selected ingredients, especially for the seal layer and the skin layer, provides a film with low seal initiation temperature (SIT), low hot tack temperature and improved high hot tack. Improvements in optical properties such as haze are achieved together with improved sealing properties, especially improved hot tack. Summary of the invention

[0021] Thus, the present invention relates to a multilayer polyethylene film comprising at least a layer (A) as a seal layer (SL), and a layer (B) as a skin layer (SKL);

[0022] Wherein, the sealing layer (SL) comprises:

[0023] i) 30.0 wt% to 100 wt% of a first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1), based on the total weight of the sealing layer (SL), having the following properties

[0024] Density 905 to 930 kg / m 3 within the range (ISO 1183);

[0025] MFR2 (190°C, 2.16kg, ISO 1133) in the range of 0.1 to 2.0 g / 10 min;

[0026] MFR 21 The ratio of MFR (190°C, 21.6 kg, ISO 1133) to MFR2 (190°C, 2.16 kg, ISO 1133), i.e. MFR21 / MFR2, in the range of 22 to 70;

[0027] Wherein, the first multimodal metallocene-catalyzed linear low-density polyethylene (mLLDPE-1) is composed of the following

[0028] (i) 30.0 to 70.0 wt% of a polyethylene component (A) consisting of ethylene polymer fractions (A-1) and (A-2); and

[0029] (ii) 70.0 to 30.0 wt% of a polyethylene component (B),

[0030] The total amount of (A) and (B) is 100.0 wt%; and

[0031] ii) 0.0 wt% to 70 wt% of ethylene-1-octene or ethylene-1-butene plastomer having the following properties

[0032] Density 860 to 910 kg / m 3 within the range of (ISO 1183); and

[0033] MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.5 to 10.0 g / 10 min; and

[0034] The surface layer (SKL) comprises:

[0035] 60.0wt% to 100.0wt% of high density polyethylene (HDPE) based on the total weight of the skin layer (SKL) with a density of 945 to 970kg / m 3 range (ISO 1183).

[0036] In one embodiment, the present invention provides a multilayer polyethylene film comprising at least a layer (A) as a sealing layer (SL), a layer (B) as a skin layer (SKL) and a layer (C) as a core layer (CL), wherein the core layer (CL) is located between the sealing layer (SL) and the skin layer (SKL), wherein layers (A) and (B) are as defined above, and the core layer (CL) comprises:

[0037] x) 50.0 wt% to 99.0 wt% of a multimodal Ziegler-Natta catalyzed linear low density polyethylene (znLLDPE-1) having a density of 920 to 950 kg / m 3 In the range of , MFR5 (190°C, 5kg, ISO1133) is in the range of 0.1 to 4.0 g / 10 min; and

[0038] y) from 1.0 wt% to 50.0 wt%, based on the total weight of the core layer (CL), of a second multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) having the following properties

[0039] Density 905 to 930 kg / m 3 within the range of (ISO 1183); and

[0040] MFR2 (190°C, 2.16kg, ISO 1133) in the range of 0.1 to 2.0 g / 10 min;

[0041] The total amount of x)+y) is 100 wt%.

[0042] definition

[0043] When the word "comprising" is used in this specification and claims, it does not exclude other non-specified elements of major or minor functional importance. For the purposes of the present invention, the term "consisting of" is considered to be a preferred embodiment of the term "comprising". If a group is defined below to include at least a certain number of embodiments, it is also understood that it discloses a group that preferably consists of only these embodiments.

[0044] Whenever the terms "including" and "having" are used, these terms have the same meaning as "comprising" as defined above.

[0045] When an indefinite or definite article is used when referring to a singular noun, this includes the plural of that noun unless something else is specifically stated.

[0046] Metallocene-catalyzed linear low density polyethylene (mLLDPE) is defined in the present invention as a linear low density polyethylene copolymer prepared in the presence of a metallocene catalyst.

[0047] Ziegler-Natta catalyzed linear low density polyethylene (znLLDPE) is defined herein as a linear low density polyethylene copolymer produced in the presence of a Ziegler-Natta catalyst.

[0048] The term "multimodal" in the context of the multimodal linear low density polyethylene herein refers to multimodality with respect to the melt flow rate (MFR). The multimodal linear low density polyethylene may have multimodality with respect to one or more other property aspects, such as density, comonomer type and / or comonomer content, as will be described below.

[0049] The first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) used according to the present invention as defined above, below or in the claims is herein also referred to as mLLDPE-1 in short.

[0050] The second multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) used according to the present invention as defined above, below or in the claims is herein also referred to as mLLDPE-2 in short.

[0051] The multimodal Ziegler-Natta catalyzed linear low density polyethylene (znLLDPE) used according to the present invention as defined above, below or in the claims is herein also referred to as znLLDPE for short.

[0052] The (multimodal) high density polyethylene (HDPE) used according to the invention as defined above, below or in the claims is herein also referred to as HDPE for short.

[0053] For the purposes of the present invention, "mLLDPE and znLLDPE or HDPE consisting of component (A) and component (B)" means polyethylene produced in at least two-stage sequential polymerization processes, wherein a first component (A) is produced first and then component (B) is produced in a subsequent polymerization step in the presence of component (A) to obtain polyethylene; or vice versa, i.e. a first component (B) is produced first and then component (A) is produced in a subsequent polymerization step in the presence of component (B) to obtain polyethylene.

[0054] Polyethylene produced in a multistage process is also known as an "in-situ" or "reactor" blend. The final product consists of an intimate mixture of polymers from two or more reactors whose different molecular weight distribution curves together form a molecular weight distribution curve with one broad maximum or two or more maxima, i.e. the final product is a multimodal polymer mixture.

[0055] Detailed description of the invention

[0056] The film of the present invention is a multilayer polyethylene film comprising at least layer (A) and layer (B).

[0057] At least two layers, ie (A) and (B), each consist of polyethylene polymer only, ie no other polymers than vinyl polymer.

[0058] In one embodiment of the present invention, the multilayer polyethylene film comprises at least layer (A), layer (B) and layer (C).

[0059] Furthermore, layer (C) consists only of polyethylene polymer.

[0060] Layer (A), Sealing layer (SL)

[0061] The layer (A) of the multilayer film of the present invention is a sealing layer (SL) comprising

[0062] i) 30.0 wt% to 100 wt% of a first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1), based on the total weight of the sealing layer (SL), and

[0063] ii) 0.0 wt% to 70 wt% of ethylene-1-octene or ethylene-1-butene plastomer having the following properties

[0064] Density 860 to 910 kg / m 3 within the range of (ISO 1183); and

[0065] MFR2 (190°C, 2.16 kg, ISO 1133) is in the range of 0.5 to 10.0 g / 10 min.

[0066] In one embodiment of the present invention, low density polyethylene (LDPE) may be added as an alternative polyethylene-based polymer instead of a plastomer. The total amount of the LDPE is 0.0 to 30.0 wt % based on the total weight of the sealing layer (SL), wherein the density of the optional low density polyethylene (LDPE) is between 910 and 940 kg / m 3 The MFR2 (ISO1133, 2.16 kg, 190°C) is in the range of 0.05 to 2.0 g / 10 min.

[0067] Preferably, a plastomer is added as the second polyvinyl polymer.

[0068] More preferably, the sealing layer (SL) consists of a first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1).

[0069] The first multimodal metallocene-catalyzed linear low-density polyethylene (mLLDPE-1)

[0070] The first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) has a density (ISO 1183) in the range of 905 to 930 kg / m 3 In the range of 908 to 925 kg / m 3 In the range of 910 to 920 kg / m 3 In the range of 912 to 918 kg / m 3 .

[0071] The MFR2 (190°C, 2.16 kg, ISO 1133) of the first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) is in the range of 0.1 to 2.0 g / 10 min, preferably 0.5 to 1.8 g / 10 min, more preferably 0.8 to 1.5 g / 10 min, such as 0.9 to 1.3 g / 10 min.

[0072] The MFR of the first multimodal metal-catalyzed linear low density polyethylene (mLLDPE-1) is 21 The ratio of MFR (190℃, 21.6kg, ISO1133) to MFR2 (190℃, 2.16kg, ISO 1133), i.e. MFR 21 / MFR2 ranges from 22 to 70, preferably from 25 to 50, more preferably from 28 to 35.

[0073] The first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) is a copolymer of ethylene and at least two different comonomers selected from α-olefins having 4 to 10 carbon atoms, such as 1-butene, 1-hexene, 1-octene, preferably 1-butene and 1-hexene.

[0074] The total amount of 1-butene is preferably in the range of 0.1 to 3.0 wt%, preferably in the range of 0.2 to 2.5 wt%, more preferably in the range of 0.3 to 2.0 wt%, based on the multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1).

[0075] The total amount of 1-hexene is preferably in the range of 2.0 to 20.0 wt%, preferably in the range of 4.0 to 18.0 wt%, more preferably in the range of 6.0 to 15.0 wt%, based on the multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1).

[0076] The sealing layer (SL) of the first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) consists of

[0077] (i) 30.0 to 70.0 wt% of a polyethylene component (A), and

[0078] (ii) 70.0 to 30.0 wt% of a polyethylene component (B).

[0079] The total amount of (A) and (B) is 100.0 wt%.

[0080] Furthermore, the polyethylene component (A) consists of ethylene polymer fractions (A-1) and (A-2).

[0081] It is possible to produce fraction (A-1) first and then produce fraction (A-2) in the presence of fraction (A-1) in a subsequent reactor, or vice versa, i.e. produce fraction (A-2) first and then produce fraction (A-1) in the presence of fraction (A-2) in a subsequent reactor. It is preferred to produce fraction (A-1) first.

[0082] The multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) is referred to herein as "multimodal" because the polyethylene component (A) comprising ethylene polymer fractions (A-1) and (A-2), and the polyethylene component (B) are produced under different polymerization conditions, resulting in different melt flow rates (MFR, e.g. MFR2). That is, the multimodal polyethylene is multimodal at least with respect to the difference in MFR of the polyethylene components (A) and (B).

[0083] Preferably, the α-olefin comonomer having 4 to 10 carbon atoms of the polyethylene component (A) is different from the α-olefin comonomer having 4 to 10 carbon atoms of the polyethylene component (B); more preferably, the α-olefin comonomer having 4 to 10 carbon atoms of the polyethylene component (A) is selected from 1-butene, 1-hexene and 1-octene, more preferably 1-butene; and the α-olefin comonomer having 4 to 10 carbon atoms of the polyethylene component (B) is preferably selected from 1-hexene and 1-octene, more preferably 1-hexene.

[0084] The comonomer type of polymer fractions (A-1) and (A-2) is the same, so fractions (A-1) and (A-2) use the same α-olefin comonomer having 4 to 10 carbon atoms, and more preferably both fractions use 1-butene as the comonomer.

[0085] Thus, in a preferred embodiment, the polyethylene component (A) is an ethylene-1-butene polymer component (A) and the polyethylene component (B) is an ethylene-1-hexene polymer component (B).

[0086] The total amount (wt%) of 1-butene present in the ethylene-1-butene polymer component (A) is 0.5 to 8.0 wt%, preferably 0.6 to 6.0 wt%, more preferably 0.8 to 5.0 wt%, even more preferably 1.0 to 4.0 wt%, based on the ethylene-1-butene polymer component (A).

[0087] The total amount (wt%) of 1-hexene present in the ethylene-1-hexene polymer component (B) is 8.0 to 25.0 wt%, preferably 9.0 to 22.0 wt%, more preferably 10.0 to 20.0 wt%, based on the ethylene-1-hexene polymer component (B).

[0088] The ethylene polymer components (A) and (B) differ in their MFR2.

[0089] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer component (A) is in the range of 2.0 to 400 g / 10 min, preferably 2.5 to 300 g / 10 min, more preferably 3.0 to 200 g / 10 min, even more preferably 3.2 to 100 g / 10 min, still more preferably 3.5 to 70.0 g / 10 min, such as 3.8 to 50.0 g / 10 min.

[0090] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer component (B) is in the range of 0.001 to 1.5 g / 10 min, preferably 0.005 to 1.0 g / 10 min, more preferably 0.01 to 0.8 g / 10 min, even more preferably 0.02 to 0.5 g / 10 min.

[0091] The MFR2 of the ethylene polymer fractions (A-1) and (A-2) may be different or the same.

[0092] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer fraction (A-1) is in the range of 1.0 to 800.0 g / 10 min, preferably 1.5 to 400.0 g / 10 min, more preferably 1.8 to 200.0 g / 10 min, even more preferably 2.0 to 50.0 g / 10 min, such as 2.1 to 40.0 g / 10 min.

[0093] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer fraction (A-2) is in the range of 2.0 to 400.0 g / 10 min, preferably 2.5 to 200.0 g / 10 min, more preferably 3.0 to 100.0 g / 10 min, most preferably 3.5 to 80.0 g / 10 min.

[0094] In one embodiment of the present invention, preferably, the ratio of the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene-1-butene polymer component (A) to the MFR2 (190°C, 2.16 kg, ISO 1133) of the final multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE) is at least 3.0 to 120.0, preferably 3.5 to 100.0, more preferably 4.0 to 90.0.

[0095] The density of the ethylene polymer component (A) is in the range of 920 to 950 kg / m 3 In the range of 925 to 948 kg / m 3 , more preferably 930 to 945 kg / m 3 , and / or the density of the ethylene polymer component (B) is from 885 to 918 kg / m3 In the range of 888 to 915 kg / m 3 , more preferably 890 to 912 kg / m 3 .

[0096] The densities of the ethylene polymer fractions (A-1) and (A-2) may be different or the same.

[0097] The density of the polymer fraction (A-1) is between 920 and 950 kg / m 3 In the range of 925 to 948 kg / m 3 , more preferably 930 to 946 kg / m 3 , such as 935 to 945 kg / m 3 .

[0098] The density of the polymer fraction (A-2) is between 920 and 950 kg / m 3 In the range of 925 to 945 kg / m 3 .

[0099] Within the scope of the present invention, the first and second ethylene polymer fractions (A-1 and A-2) of the polyethylene component (A) are present in a weight ratio of 4:1 to 1:4, such as 3:1 to 1:3, or 2:1 to 1:2, or 1:1.

[0100] The polyethylene component (A) is present in an amount of 30.0 to 70.0 wt%, preferably 32.0 to 55.0 wt%, even more preferably 34.0 to 45.0 wt%, based on the multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1).

[0101] Therefore, the content of the polyethylene component (B) is 70.0 to 30.0 wt%, preferably 68.0 to 45.0 wt%, more preferably 66.0 to 55.0 wt%, based on the multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1).

[0102] Since the polyethylene component (A) of the multimodal metallocene-catalyzed linear low-density polyethylene (mLLDPE-1) consists of ethylene polymer fractions (A-1) and (A-2), the multimodal metallocene-catalyzed linear low-density polyethylene (mLLDPE-1) can be produced by a three-stage process, preferably comprising a first slurry reactor (loop reactor 1), wherein the first slurry loop reactor is connected in series with another slurry reactor (loop reactor 2); so that the first ethylene polymer fraction (A-1) produced in the loop reactor 1 is fed into the loop reactor 2, wherein the second ethylene polymer fraction (A-2) is produced in the presence of the first fraction (A-1). Fraction (A-1) can be produced first, and then fraction (A-2) can be produced in the presence of fraction (A-1) in a subsequent reactor; or vice versa, i.e., fraction (A-2) is produced first, and then fraction (A-1) is produced in the presence of fraction (A-2) in a subsequent reactor. Preferably, fraction (A-1) is produced first.

[0103] The loop reactor 2 is then connected in series to a gas phase reactor (GPR) such that the first polyethylene fraction (A) leaving the second slurry reactor is fed to the GPR to produce a trimodal polyethylene copolymer. In this case, the reaction conditions in the two slurry reactors are selected such that the products produced in the two slurry reactors differ in MFR and / or density.

[0104] Such processes are described in WO 2016 / 198273, WO 2021009189, WO 2021009190, WO 2021009191 and WO 2021009192. Detailed information on how to prepare suitable multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) can be found in these references.

[0105] A suitable process is the Borstar PE process or the Borstar PE 3G process.

[0106] Therefore, the multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) according to the present invention is preferably produced in a loop gas cascade. This polymerization step may be preceded by a prepolymerization step. The purpose of the prepolymerization is to polymerize a small amount of polymer onto the catalyst under conditions of low temperature and / or low monomer concentration. By prepolymerization, the performance of the catalyst in the slurry can be improved and / or the properties of the final polymer can be improved. The prepolymerization step is preferably carried out in the slurry, and the amount of polymer produced in the optional prepolymerization step should be counted as the amount (wt%) of the polyethylene component (A).

[0107] When there is a prepolymerization step, preferably all of the catalyst components are introduced into the prepolymerization step. However, if the solid catalyst component and the cocatalyst can be fed separately, only part of the cocatalyst can be introduced into the prepolymerization stage, and the remaining part into the subsequent polymerization stage. Moreover, in this case, it is necessary to introduce enough cocatalyst into the prepolymerization stage in order to obtain a sufficient polymerization reaction therein.

[0108] It is understood that within the scope of the present invention the amount of polymer produced in the prepolymerisation is within 1 to 5 wt% relative to the final metallocene-catalysed multimodal metallocene-catalysed linear low density polyethylene (mLLDPE-1) and can be counted as part of the first polyethylene component (A).

[0109] catalyst /

[0110] The mLLDPE-1 used in the present invention is prepared using a metallocene catalyst. The metallocene catalyst comprises a metallocene complex and a cocatalyst. The metallocene compound or complex is also referred to herein as an organometallic compound (C).

[0111] The organometallic compound (C) comprises a transition metal (M) of Groups 3 to 10 of the Periodic Table of Elements (IUPAC 2007) or an actinide or lanthanide.

[0112] The term "organometallic compound (C)" according to the present invention comprises any metallocene or non-metallocene compound of a transition metal which has at least one organic (coordinating) ligand and which exhibits catalytic activity alone or together with a cocatalyst. Transition metal compounds are well known in the art and the present invention encompasses metal compounds of Groups 3 to 10, such as Groups 3 to 7, or Groups 3 to 6, such as Groups 4 to 6 of the Periodic Table of the Elements (IUPAC 2007), as well as lanthanides or actinides.

[0113] In one embodiment, the organometallic compound (C) has the following formula (I):

[0114]

[0115] Wherein, each X is independently a halogen atom, C 1-6 Alkyl, C 1-6 alkoxy, phenyl or benzyl;

[0116] Each Het is independently a monocyclic heteroaryl group containing at least one heteroatom selected from O or S;

[0117] L is -R'2Si-, wherein each R' is independently a C substituted with an alkoxy group having 1 to 10 carbon atoms. 1-10 Alkyl or C 1-20 Hydrocarbon;

[0118] M is Ti, Zr or Hf;

[0119] Each R 1 Same or different, C 1-6 Alkyl or C 1-6 Alkoxy;

[0120] Each n is 1 to 2;

[0121] Each R 2 Same or different, C 1-6 Alkyl, C 1-6 Alkoxy or -Si(R)3 group;

[0122] Each R is composed of 1 to 3 C 1-6 Alkyl optionally substituted C 1-10 Alkyl or phenyl; and

[0123] Each p is from 0 to 1.

[0124] Preferably, the compound of formula (I) has the structure

[0125]

[0126] Wherein, each X is independently a halogen atom, C 1-6 Alkyl, C 1-6 alkoxy, phenyl or benzyl;

[0127] L is Me2Si-;

[0128] Each R 1 Same or different, C 1-6 an alkyl group, such as methyl or tert-butyl;

[0129] Each n is 1 to 2;

[0130] R 2 is -Si(R)3alkyl; each p is 1;

[0131] Each R is C 1-6 Alkyl or phenyl.

[0132] Highly preferred complexes of formula (I) are

[0133]

[0134] Most preferably, dimethylsilanediylbis[2-(5-trimethylsilylfuran-2-yl)-4,5-dimethylcyclopentadien-1-yl]zirconium dichloride complex is used.

[0135] More preferably, the polyethylene components (A) and (B) of mLLDPE-1 are produced using the same metallocene catalyst, ie, in the presence of the same metallocene catalyst.

[0136] To form the catalyst, a cocatalyst, also called an activator, well known in the art is used. Cocatalysts containing Al or B are also well known and can be used here. Methylaluminoxane (such as MAO) or a boron-based cocatalyst (such as a borate) is preferably used.

[0137] Unlike Ziegler-Natta catalysis, polyethylene copolymers made using single-site catalysis have characteristics that distinguish them from Ziegler-Natta materials. In particular, the distribution of the comonomer is more uniform. This can be demonstrated using TREF or Crystaf techniques. Catalyst residues can also indicate the catalyst used. For example, Ziegler-Natta catalysts do not contain Zr or Hf Group (IV) metals.

[0138] mLLDPE-1 may optionally contain additives and / or fillers.

[0139] Optional additives and fillers and their amounts are conventional in the film application field. Examples of such additives are antioxidants, processing stabilizers, UV stabilizers, pigments, fillers, antistatic additives, antiblocking agents, nucleating agents, acid scavengers and polymer processing agents (PPA) and the like.

[0140] Ethylene-1-octene or ethylene-1-butene plastomers

[0141] The sealing layer (SL) may contain ethylene-1-octene or ethylene-1-butene plastomer as an additional polyethylene-based polymer in an amount of 0.0 wt % to 70.0 wt %.

[0142] In case of adding plastomer as additional polyethylene-based polymer, the amount of plastomer ranges from 20.0 wt% to 65.0 wt%, preferably from 30.0 wt% to 60.0 wt%, based on the total weight of the sealing layer (SL).

[0143] The density (ISO1183) of the ethylene-1-octene or ethylene-1-butene plastomer is between 860 and 910 kg / m 3 In the range of 870 to 908 kg / m 3 , more preferably 880 to 905 kg / m 3 .

[0144] The MFR2 (190°C, 2.16 kg, ISO 1133) of the plastomer is in the range of 0.5 to 10.0 g / 10 min, preferably 0.8 to 8.0 g / 10 min, more preferably 0.9 to 5.0 g / 10 min, such as 0.9 to 3.5 g / 10 min.

[0145] A preferred plastomer is ethylene-1-octene plastomer.

[0146] The content of comonomer, such as 1-octene, in the plastomer may be in the range of 5.0 to 40.0 wt%, such as 12.0 to 30.0 wt%.

[0147] The molecular weight distribution Mw / Mn of suitable plastomers is usually less than 4, such as 3.8 or less, but at least 2.0, preferably between 3.7 and 2.1.

[0148] Suitable ethylene-1-butene or ethylene-1-octene plastomers may be any copolymers of ethylene with 1-butene or 1-octene having the above-defined properties, which copolymers are commercially available, for example, from Borealis under the trade name Queo, such as Queo 8201 or Queo 0201, from DOW Chemical Company, USA, under the trade name Engage or Affinity, or from Mitsui Chemicals under the trade name Tafmer.

[0149] Alternatively, these plastomers may also be prepared by a one-stage or two-stage polymerization process by known techniques, comprising solution polymerization, slurry polymerization, gas phase polymerization, or a combination thereof, in the presence of a suitable catalyst known to those skilled in the art, such as a vanadium oxide catalyst or a single-site catalyst, e.g., a metallocene catalyst or a constrained geometry catalyst. The plastomers of the present invention are ideally formed using a metallocene-type catalyst.

[0150] Preferably, these plastomers are prepared by a one-stage or two-stage solution polymerization process, in particular by a high temperature solution polymerization process at a temperature above 100°C.

[0151] This process is essentially based on the polymerization of monomers and suitable comonomers in a liquid hydrocarbon solvent in which the resulting polymer is soluble. The polymerization reaction is carried out at a temperature above the melting point of the polymer, as a result of which a polymer solution is obtained. This solution is flashed in order to separate the polymer from the unreacted monomers and the solvent. The solvent is then recovered and recycled in the process.

[0152] The solution polymerization process is preferably a high temperature solution polymerization process, using a polymerization temperature above 100° C. More preferably, the polymerization temperature is at least 110° C., more preferably at least 150° C. The polymerization temperature may be as high as 250° C.

[0153] The pressure in this solution polymerization process is preferably in the range of 10 to 100 bar, preferably 15 to 100 bar, more preferably 20 to 100 bar. The liquid hydrocarbon solvent used is preferably a C5-12 hydrocarbon that is unsubstituted or substituted with a C1-4 alkyl group, such as pentane, methylpentane, hexane, heptane, octane, cyclohexane, methylcyclohexane and hydrogenated naphtha. More preferably, an unsubstituted C6-10 hydrocarbon solvent is used.

[0154] A known solution technology suitable for use in the process of the present invention is Borceed TM technology.

[0155] Low-density polyethylene (LDPE)

[0156] The sealing layer (SL) may contain no plastomer but may contain 0.0 wt% to 30.0 wt% of low density polyethylene (LDPE) as an additional polyethylene-based polymer.

[0157] In case LDPE is added as the additional polyethylene-based polymer, the amount of LDPE ranges from 5.0 to 30.0% wt%, preferably from 15.0 to 25.0 wt%, based on the total weight of the sealing layer (SL).

[0158] The density of the optional LDPE is between 910 and 940 kg / m 3 The MFR2 (ISO1133, 2.16 kg, 190°C) is in the range of 0.05 to 2.0 g / 10 min.

[0159] The low density polyethylene (LDPE) is preferably a low density polyethylene produced in a high pressure process.

[0160] Such LDPEs are well known in the art, and they typically contain long chain branches which distinguish LDPE from linear low density polyethylene (LLDPE).

[0161] The density (ISO1183) of the LDPE is preferably between 912 and 938 kg / m 3 In the range of 914 to 935 kg / m 3 In the range of 915 to 925 kg / m 3 within the range.

[0162] Furthermore, the melt flow rate MFR2 (ISO 1133, 2.16 kg, 190° C.) of the LDPE is preferably in the range of 0.08 to 1.9 g / 10 min, more preferably in the range of 0.10 to 1.8 g / 10 min, even more preferably in the range of 0.15 to 1.5 g / 10 min.

[0163] The Tm (DSC, ISO 11357-3) of the LDPE is preferably in the range of 70 to 180°C, more preferably 90 to 140°C, such as about 110 to 120°C.

[0164] The LDPE suitable for layer (A) can be any conventional LDPE, for example, LDPE known on the market, or they can be prepared according to any conventional high pressure polymerization (HP) process in a tubular reactor or an autoclave reactor using free radical formation. Such high pressure processes are well known in the field of polymer chemistry.

[0165] Typical pressures are from 1000 to 3000 bar. The polymerization temperature is preferably in the range of 150 to 350° C. Free radical initiators are well known, for example organic peroxide initiators.

[0166] Suitable LDPE is available from Borealis, Basell, Exxon, Sabic or other suppliers.

[0167] Layer (B), Surface layer (SKL)

[0168] Layer (B) is the skin layer (SKL) of the multilayer film, which comprises

[0169] a) 60.0 wt% to 100.0 wt% based on the total weight of the skin layer (SKL) of a multimodal high density polyethylene (HDPE) having a density of 945 to 970 kg / m 3 The MFR2 (190°C, 2.16 kg, ISO 1133) is in the range of 0.1 to 2.0 g / 10 min.

[0170] As an additional polymer, based on the total weight of the skin layer (SKL), 0.0 to 40.0 wt%, preferably 5.0 to 30.0 wt%, more preferably 10.0 to 25.0 wt%, of ethylene-1-octene or ethylene-1-butene plastomer is added, and its density is 860 to 910 kg / m 3 (ISO 1183) range, MFR2 (190 ° C, 2.16 kg, ISO 1133) range of 0.5 to 10.0 g / 10 min; and / or linear low density polyethylene (LLDPE) with a density range of 910 to 945 kg / m 3(ISO 1183), MFR2 (ISO 1133, 2.16 kg, 190°C) is in the range of 0.1 to 2.0 g / 10 min.

[0171] Suitable plastomers are as described above for layer (A).

[0172] Suitable LLDPEs are, for example, znLLDPE as described below for the core layer (CL); or metallocene-catalyzed linear low density polyethylene, for example for the seal layer (SL) or the core layer (CL), or commercially available mLLDPE, such as FK1820 (Borealis or Borouge); or Total's Supertough grades (such as 40ST05 or 22ST05).

[0173] Preferably, the skin layer (SKL) consists of high density polyethylene (HDPE).

[0174] High-density polyethylene (HDPE)

[0175] The density of the high-density polyethylene (HDPE) is between 945 and 970 kg / m 3 The range of (ISO 1183), preferably 948 to 968 kg / m 3 , more preferably 950 to 965 kg / m 3 , such as 951 to 962 kg / m 3 .

[0176] The MFR2 (190° C., 2.16 kg, ISO 1133) of the HDPE is in the range of 0.1 to 3.0 g / 10 min, preferably 0.2 to 2.5 g / 10 min, more preferably 0.5 to 2.0 g / 10 min.

[0177] The MFR5 (190° C., 5 kg, ISO 1133) of the HDPE may be in the range of 1.0 to 10.0 g / 10 min, preferably 1.5 to 8.0 g / 10 min, more preferably 2.0 to 6.0 g / 10 min.

[0178] The MFR of HDPE 21 (190° C., 21.6 kg, ISO 1133) may be in the range of 20.0 to 100.0 g / 10 min, preferably 25.0 to 80.0 g / 10 min, and more preferably 30.0 to 60.0 g / 10 min.

[0179] The HDPE has a melt flow rate ratio of FRR21 / 5 (MFR 21 / MFR5) can be 5 to 30, preferably 7 to 25, most preferably 8 to 20.

[0180] The melting temperature (Tm) of the HDPE may be in the range of 128°C to 140°C, preferably 129°C to 135°C.

[0181] The HDPE can be produced using either a metallocene catalyst system or a Ziegler-Natta catalyst system.

[0182] Metallocene catalyst system

[0183] As the metallocene catalyst system, the catalyst system of mLLDPE-1 described above can be used.

[0184] Alternatively, it is also possible to use metallocene complexes of the formula (II).

[0185] (Cp)2R n MX2 (II)

[0186] in:

[0187] Each Cp is independently an unsubstituted or substituted and / or fused cyclopentadienyl ligand, for example, a substituted or unsubstituted cyclopentadienyl, substituted or unsubstituted indenyl or substituted or unsubstituted fluorenyl ligand;

[0188] The optional substituent(s) are preferably independently selected from halogen, hydrocarbon (e.g. C1-C 20 Alkyl, C2-C 20 Alkenyl, C2-C 20 Alkynyl, C3-C 12 Cycloalkyl, C6-C 20 Aryl or C7-C 20 Arylalkyl), C3-C 12 Cycloalkyl, C6-C 20 Heteroaryl, C1-C 20 Haloalkyl, -SiR"3, -OSiR"3, -SR", -PR"2, OR" or -NR"2;

[0189] Each R" is independently hydrogen or a hydrocarbon group, such as C1-C 20 Alkyl, C2-C 20 Alkenyl, C2-C 20 Alkynyl, C3-C 12 Cycloalkyl or C6-C 20 Aryl; or, for example, in the case of -NR"2, the two substituents R" may form a ring together with the nitrogen atom to which they are attached, such as a five-membered or six-membered ring;

[0190] R is a bridge composed of 1-7 atoms, for example, a bridge composed of 1-4 C atoms and 0-4 heteroatoms, wherein the heteroatoms may be, for example, Si, Ge and / or O atoms, wherein each bridge atom may independently carry a substituent, for example, C1-C 20 Alkyl, tri(C1-C 20 Alkyl)silyl, tri(C1-C 20 Alkyl)silyl or C6-C 20 aryl substituent); or a bridge consisting of 1-3 heteroatoms, such as one or two heteroatoms, such as silicon, germanium and / or oxygen atoms, such as -SiR 2 2-, where each R 2 Independently C1-C 20 Alkyl, C 3-12 Cycloalkyl, C6-C 20 Aryl or tri(C1-C 20 alkyl)silyl residues, for example trimethylsilyl;

[0191] M is a Group 4 transition metal, such as Ti, Zr or Hf, especially Zr or Hf;

[0192] Each X is independently a sigma ligand, such as H, halogen, C1-C 20 Alkyl, C1-C 20 Alkoxy, C2-C 20 Alkenyl, C2-C 20 Alkynyl, C3-C 12 Cycloalkyl, C6-C 20 Aryl, C6-C 20 Aryloxy, C7-C 20 Aralkyl, C7-C 20 aralkenyl, -SR", -PR"3, -SiR"3, -OSiR"3, -NR"2, or -CH2-Y, wherein Y is C6-C 20 Aryl, C6-C 20 -heteroaryl, C1-C 20 Alkoxy, C6-C 20 Aryloxy, NR"2, -SR", -PR"3, -SiR"3 or -OSiR"3;

[0193] Each of the above, alone or in combination with Cp, X, R" or R 2 The ring structure which is part of another structure in the form of a substituent may be further replaced by a C1-C1-C2-substituted ring which may contain Si and / or O atoms. 20 Alkyl substitution;

[0194] n is 0 or 1.

[0195] Suitably, in each X being -CH2-Y, each Y is independently selected from C6-C20 Most preferably, X as -CH2-Y is benzyl. Each X other than -CH2-Y is independently halogen, C1-C 20 Alkyl, C1-C 20 Alkoxy, C6-C 20 Aryl, C7-C 20 Arylalkenyl or -NR"2 as defined above, for example -N(C1-C 20 Alkyl)2.

[0196] Preferably, each X is halogen, methyl, phenyl or -CH2-Y, each Y is independently as defined above, more preferably, X is halogen or methyl.

[0197] Preferably, Cp is cyclopentadienyl, indenyl, tetrahydroindenyl or fluorenyl, optionally substituted as defined above. More preferably, Cp is cyclopentadienyl or indenyl, even more preferably Cp is cyclopentadienyl.

[0198] In a suitable subgroup of compounds of formula (II), each Cp independently carries 1, 2, 3 or 4 substituents as defined above, preferably 1, 2 or 3, such as 1 or 2 substituents, which are preferably selected from C1-C 20 Alkyl, C6-C 20 Aryl, C7-C 20 Aralkyl (wherein the aryl ring, alone or as part of another structure, may be further substituted as described above), -OSiR"3, wherein R" is as described above, preferably C1-C 20 alkyl.

[0199] If present, R is preferably a methylene, ethylene or silyl bridge, wherein the silyl group may be substituted as defined above, for example (dimethyl)Si=, (methylphenyl)Si=, (methylcyclohexyl)silyl= or (trimethylsilylmethyl)Si=;

[0200] n is 0 or 1, preferably 0.

[0201] The preparation of metallocene can be carried out according to or similarly from the method known in the literature, and is within the skill range of those skilled in the art. Therefore, for this preparation method, reference is made to EP-A-129 368 for example, wherein the metal atom carries -NR "2 example reference is made to the compound of part for example WO9856831 and WO0034341. For this preparation method, reference is also made to EP260130A, WO9728170, WO9846616, WO9849208, WO9912981, WO9919335, WO9856831, WO00 / 34341, EP423101A and EP537130A for example.

[0202] The most preferred metallocene complex is bis(1-methyl-3-n-butylcyclopentadienyl)zirconium(IV) chloride.

[0203] Ziegler-Natta catalyst system

[0204] A suitable Ziegler-Natta catalyst comprises a magnesium compound, an aluminum compound and a titanium compound supported on a particulate support.

[0205] The particle support may be an inorganic oxide support, such as silica, alumina, titania, silica-alumina and silica-titania. Preferably, the support is silica.

[0206] The average particle size of the silica support is generally between 10 and 100 μm. However, it has proven to be particularly advantageous if the average particle size of the support is between 15 and 30 μm, preferably between 18 and 25 μm.

[0207] The magnesium compound is the reaction product of a dialkylmagnesium and an alcohol. The alcohol is a linear or branched aliphatic monohydric alcohol. Preferably, the alcohol has 6 to 16 carbon atoms. Particularly preferred are branched alcohols, an example of a preferred alcohol is 2-ethyl-1-hexanol. The dialkylmagnesium can be any compound in which magnesium is bonded to two identical or different alkyl groups. Butyloctylmagnesium is an example of a preferred dialkylmagnesium.

[0208] The aluminum compound is a chlorine-containing alkyl aluminum. Particularly preferred compounds are alkyl aluminum dichlorides and alkyl aluminum sesquichlorides.

[0209] The titanium compound is a halogen-containing titanium compound, preferably a chlorine-containing titanium compound. A particularly preferred titanium compound is titanium tetrachloride.

[0210] The catalyst can be prepared by contacting the support with the above compounds in sequence as described in EP-A-688794. Alternatively, the catalyst can be prepared by first preparing a solution of the components and then contacting the solution with the support as described in WO-A-01 / 55230.

[0211] The above-mentioned fixed catalyst component can be used for polymerization after contacting with alkyl aluminum cocatalyst (preferably trialkyl aluminum compound). The contact between the solid catalyst component and the alkyl aluminum cocatalyst can be carried out before the catalyst is introduced into the polymerization reactor, or it can be carried out by introducing the two components into the polymerization reactor separately.

[0212] Suitable Ziegler-Natta catalysts and methods for their production are described in EP1378528.

[0213] The HDPE may be unimodal or multimodal.

[0214] Implementation (I)

[0215] In embodiment (I), the HDPE is unimodal and is produced in one polymerization stage or in two polymerization stages, wherein the same reaction conditions are employed in both stages so that the same polymer is produced in both stages.

[0216] The properties of this unimodal HDPE are as described above.

[0217] Preferably, the HDPE is a multimodal HDPE.

[0218] The preferred multimodal high density polyethylene (HDPE) is called "multimodal" because it is produced by at least a two stage polymerisation process in which at least two different polyethylene fractions having different properties, i.e. different density and MFR, are produced.

[0219] In one embodiment the multimodal high density polyethylene (HDPE) consists of two polyethylene fractions (D) and (E), thus being a bimodal HDPE, wherein the bimodal HDPE is produced by a two stage polymerisation process.

[0220] In another embodiment the polyethylene component (D) consists of ethylene polymer fractions (D-1) and (D-2), whereby the multimodal HDPE is a trimodal HDPE, wherein the trimodal HDPE is produced by three stage polymerisation steps.

[0221] Implementation Plan (II)

[0222] In a preferred embodiment, embodiment (II), the multimodal HDPE is a trimodal HDPE produced in the presence of a metallocene catalyst system or a Ziegler-Natta catalyst system, preferably in the presence of the above-mentioned metallocene catalyst system.

[0223] In embodiment (I), the polyethylene component (D) of the trimodal HDPE is an ethylene copolymer and the component (E) thereof is an ethylene homopolymer or copolymer.

[0224] Preferably, component (E) consists of a single ethylene homopolymer or copolymer. Component (D) is an ethylene copolymer mixture comprising (e.g. consisting of) a first ethylene copolymer fraction (D-1) and a second ethylene copolymer fraction (D-2), wherein the comonomers in the first and second ethylene copolymer fractions are the same.

[0225] In embodiment (II) of the present invention, the MFR2 of the polyethylene component (D) is preferably in the range of 10 to 400 g / 10 min, more preferably in the range of 12 to 200 g / 10 min, even more preferably in the range of 15 to 100 g / 10 min, most preferably in the range of 20 to 50 g / 10 min.

[0226] The density of the polyethylene component (D) is preferably in the range of 955 to 970 kg / m 3 In the range of 958 to 968 kg / m 3 , even more preferably 960 to 965 kg / m 3 .

[0227] As described above, in embodiment (II), the polyethylene component (D) is an ethylene copolymer. Preferred ethylene copolymers are α-olefins (e.g. C 3-12 Examples of suitable α-olefins include 1-butene, 1-hexene and 1-octene; 1-butene is a particularly preferred comonomer.

[0228] The polyethylene component (D) consists of two fractions, namely a first ethylene copolymer fraction (D-1) and a second ethylene copolymer fraction (D-2).

[0229] It is possible to produce fraction (D-1) first and then produce fraction (D-2) in the presence of fraction (D-1) in a subsequent reactor, or vice versa, i.e. produce fraction (D-2) first and then produce fraction (D-1) in the presence of fraction (D-2) in a subsequent reactor. It is preferred to produce fraction (D-1) first.

[0230] The MFR2 and / or density of fractions (D-1) and (D-2) may be the same or different.

[0231] Therefore, the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer fraction (D-1) and / or the ethylene polymer fraction (D-2) is preferably in the range of 10.0 to 80.0 g / 10 min, preferably 15.0 to 70.0 g / 10 min, more preferably 20.0 to 60.0 g / 10 min, even more preferably 30.0 to 50.0 g / 10 min.

[0232] Preferably, the MFR2 of fraction (D-1) is higher than the MFR2 of fraction (D-2).

[0233] The density of the ethylene polymer fraction (D-1) and / or (D-2) is preferably in the range of 945 to 975 kg / m 3 In the range of 950 to 970 kg / m 3, even more preferably 952 to 968 kg / m 3 .

[0234] Preferably, the density of fraction (D-2) is higher than the density of fraction (D-1).

[0235] The MFR2 of the polyethylene component (E) is preferably in the range of 0.01 to 1.0 g / 10 min, more preferably 0.02 to 0.8 g / 10 min, even more preferably 0.05 to 0.5 g / 10 min.

[0236] The density of the polyethylene component (E) is preferably in the range of 925 to 965 kg / m 3 In the range of 930 to 962 kg / m 3 , even more preferably 935 to 960 kg / m 3 .

[0237] As stated above, the polyethylene component (E) is an ethylene homopolymer or copolymer.

[0238] The expression "homopolymer" as used herein refers to polyethylene which consists essentially of, ie at least 98 wt%, preferably at least 99 wt%, more preferably at least 99.5 wt%, most preferably at least 99.8 wt%.

[0239] In the case where the polyethylene component (E) is an ethylene copolymer, the preferred ethylene copolymer is an α-olefin (e.g. C 3-12 Examples of suitable α-olefins include 1-butene, 1-hexene and 1-octene; 1-hexene is a particularly preferred comonomer.

[0240] The multimodal HDPE in embodiment (II) is produced by polymerisation using conditions which result in a multimodal (ie trimodal) polymer product.

[0241] For the polymerization process in the three-stage polymerization process, refer to the relevant description of mLLDPE-1.

[0242] Implementation (III)

[0243] In embodiment (III), the multimodal HDPE is a bimodal HDPE produced in the presence of a metallocene catalyst system or a Ziegler-Natta catalyst system (znHDPE), preferably in the presence of a Ziegler-Natta catalyst system.

[0244] The HDPE of embodiment (III) is an ethylene homopolymer or an ethylene copolymer. An ethylene copolymer is a polymer comprising ethylene monomer and one or more comonomers.

[0245] The comonomer may be an alpha-olefin having 4 to 12 carbon atoms, such as 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene.

[0246] More preferably, the HDPE of embodiment (III) is a copolymer of ethylene and 1-butene, 1-hexene or 1-octene, most preferably a copolymer of ethylene and 1-butene.

[0247] Preferably, the total amount of comonomers present in the HDPE is from 0.0 to 0.40 mol%, more preferably from 0.01 to 0.30 mol%, most preferably from 0.02 to 0.20 mol%.

[0248] The HDPE comprises or consists of a lower molecular weight (LMW) component (D) and a higher molecular weight (HMW) component (E); wherein the lower molecular weight component (D) is an ethylene homopolymer with a density of 965 to 975 kg / m 3 The higher molecular weight component (E) is an ethylene copolymer of ethylene and at least one C4 to C12 α-olefin, having a density of 935 to 955 kg / m 3 .

[0249] The lower molecular weight (LMW) component (D) has a lower molecular weight than the higher molecular weight component (E), and therefore has a higher MFR2 than the higher molecular weight (HMW) component (E).

[0250] The HDPE used according to the invention is preferably produced in the presence of a Ziegler-Natta catalyst system and is therefore a znHDPE.

[0251] You can use the one produced by Borouge FB5600 resin is used as bimodal znHDPE.

[0252] Layer (C), core layer (CL)

[0253] In one embodiment, the present invention provides a multilayer polyethylene film, which comprises at least layer (A) serving as the sealing layer (SL), layer (B) serving as the surface layer (SKL), and layer (C) serving as the core layer (CL), wherein the core layer (CL) is located between the sealing layer (SL) and the surface layer (SKL), and wherein layer (A) and layer (B) are as defined above.

[0254] The core layer (CL) comprises:

[0255] x) 50.0 wt% to 99.0 wt% of a multimodal Ziegler-Natta catalyzed linear low density polyethylene (znLLDPE-1) having a density (ISO 1183) in the range of 920 to 950 kg / m 3MFR5 (190°C, 5kg, ISO 1133) is in the range of 0.1 to 4.0 g / 10 min; and

[0256] y) from 1.0 wt% to 50.0 wt%, based on the total weight of the core layer (CL), of a second multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) having the following properties

[0257] Density 905 to 930 kg / m 3 within the range of (ISO 1183); and

[0258] MFR2 (190°C, 2.16kg, ISO 1133) in the range of 0.1 to 2.0 g / 10 min;

[0259] The sum of x)+y) is 100 wt%.

[0260] Preferably, the content of znLLDPE-1 is from 60.0 to 95.0 wt%, more preferably from 65.0 to 90.0 wt%, even more preferably from 70.0 to 85.0 wt%, based on the total weight of the core layer (CL).

[0261] Therefore, the content of mLLDPE-2 in the core layer (CL) is 5.0 to 40.0 wt%, more preferably 10.0 to 35.0 wt%, even more preferably 15.0 to 30.0 wt%, based on the total weight of the core layer (CL).

[0262] Multimodal Ziegler-Natta catalyzed linear low density polyethylene (znLLDPE-1)

[0263] Multimodal Ziegler-Natta catalyzed linear low density polyethylene (znLLDPE-1) with a density (ISO 1183) of 920 to 950 kg / m 3 In the range of 925 to 945 kg / m 3 , more preferably 928 to 942 kg / m 3 , such as 930 to 940 kg / m 3 .

[0264] The MFR5 (190°C, 5kg, ISO 1133) of znLLDPE-1 is in the range of 0.1 to 4.0 g / 10 min, preferably 0.5 to 3.5 g / 10 min, more preferably 0.7 to 3.0 g / 10 min, such as 0.8 to 2.5 g / 10 min.

[0265] znLLDPE-1 contains at least one or two comonomers. Suitable comonomers are C3-C 10 α-olefin comonomer.

[0266] Therefore, znLLDPE-1 can be ethylene and a C3-C 10 Copolymers of olefin comonomers, also ethylene and two different C3-C 10 Terpolymers of olefin comonomers.

[0267] Preferably, the comonomer is selected from 1-butene, 1-hexene and 1-octene. The comonomer used is preferably 1-butene and / or 1-hexene.

[0268] More preferred are terpolymers comprising 1-butene and 1-hexene comonomers.

[0269] The total monomer content of the znLLDPE is preferably in the range of 0.3 to 7.0 mol%, more preferably 0.6 to 4.5 mol%, even more preferably 1.5 to 3.5 mol%.

[0270] The content of 1-butene is preferably 0.1 to 3.0 mol%, more preferably 0.2 to 2.0 mol%, even more preferably 0.3 to 1.5 mol%; the content of 1-hexene is preferably 0.2 to 4.0 mol%, more preferably 0.4 to 2.5 mol%, even more preferably 0.7 to 2.0 mol%.

[0271] In one embodiment of the multilayer film of the present invention, the znLLDPE-1 used for layer (C) (core layer (CL)) comprises

[0272] (X-1) a relatively low molecular weight (LMW) ethylene homopolymer and

[0273] (X-2) Higher molecular weight (HMW) terpolymer of ethylene, 1-butene and 1-hexene.

[0274] The lower molecular weight homopolymer fraction (X-1) has a lower molecular weight than the higher molecular weight terpolymer fraction (X-2).

[0275] In another embodiment of the present invention the lower molecular weight (LMW) ethylene homopolymer (X-1) consists of one or two fractions, ie consists of one or two ethylene homopolymers.

[0276] When the lower molecular weight (LMW) ethylene homopolymer (X-1) consists of two ethylene homopolymers, the two fractions are named (LMW-1) and (LMW-2).

[0277] The lower molecular weight homopolymer (X-1) of znLLDPE-1 has a melt index MFR2 according to ISO 1133 (190°C) in the range of 200 to 1000 g / 10 min, preferably 250 to 800 g / 10 min; a density according to ISO 1183 in the range of 940 to 980 kg / m 3 In the range of 945 to 975 kg / m 3 ; The comonomer content is in the range of 0 to 2.5 mol%, preferably 0 to 2.0 mol%.

[0278] The content of the lower molecular weight fraction (X-1) of znLLDPE-1 is in the range of 30 to 60 wt%, preferably 35 to 50 wt%, more preferably 35 to 45 wt%.

[0279] The expression "ethylene homopolymer" as used herein refers to a polyethylene consisting essentially of, ie consisting of at least 98.0 wt%, preferably at least 99.0 wt%, more preferably at least 99.5 wt%, such as at least 99.8 wt% ethylene.

[0280] When the lower molecular weight (LMW) ethylene homopolymer (X1) consists of two ethylene homopolymers, fractions (LMW-1) and (LMW-2), the two fractions preferably have different MFR2 according to ISO 1133 (190°C).

[0281] The MFR2 of the homopolymer fraction (LMW-1) according to ISO 1133 (190°C) is preferably in the range of 100 to 400 g / 10 min, more preferably in the range of 150 to 300 g / 10 min, while the MFR2 of the homopolymer fraction (LMW-2) according to ISO 1133 (190°C) is preferably in the range of 450 to 1200 g / 10 min, more preferably in the range of 600 to 1100 g / 10 min.

[0282] The MFR2 of the fraction (LMW-1) is preferably lower than the MFR2 of the total low molecular weight (LMW) ethylene homopolymer (X-1).

[0283] According to a preferred embodiment, the ratio of MFR2(LMW-1) / MFR2(X-1) may be, for example, between greater than 1 and 10, preferably between 1.5 and 5, such as 1.5 and 4.

[0284] Ideally, the difference in MFR between the first and second homopolymer fractions (LMW-1) and (LMW-2) is as large as possible.

[0285] Ideally, the MFR difference between the first homopolymer fraction (LMW-1) and the MFR2 of the total low molecular weight (LMW) ethylene homopolymer (X-1) is as large as possible. For example, the MFR2 of the first homopolymer fraction (LMW-1) may be at least 50 g / 10 min lower than the MFR2 of the total low molecular weight (LMW) ethylene homopolymer (X-1), for example at least 100 g / 10 min, or 100 to 200 g / 10 min.

[0286] The density of the two homopolymer fractions (LMW-1) and (LMW-2) may be the same or different and may be between 955 and 980 kg / m 3 In the range of 965 to 980 kg / m 3 or 965 to 975 kg / m 3 .

[0287] In one embodiment of the present invention, the densities of the homopolymer fractions (LMW-1) and (LMW-2) are the same or differ by + / - 5 kg / m 3 , preferably + / -2kg / m 3 .

[0288] The total low molecular weight (LMW) ethylene homopolymer (X-1) may comprise 30 to 60 wt% of a first ethylene homopolymer fraction (LMW-1) and 70 to 40 wt% of a second ethylene homopolymer fraction (LMW-2). In some embodiments, there is an excess of the second ethylene homopolymer fraction (LMW-2), for example, the weight percentage of the second ethylene homopolymer fraction (LMW-2) is 54 to 70 wt%.

[0289] In another embodiment, the total low molecular weight (LMW) ethylene homopolymer (X-1) comprises the same amounts of the first and second ethylene homopolymer fractions (LMW-1) and (LMW-2).

[0290] The higher molecular weight fraction (X-2) has lower MFR2 and density compared to the lower molecular weight fraction (X-1).

[0291] Preferably, znLLDPE-1 is produced by a multi-stage polymerization process, such as a two-stage or three-stage polymerization using the same Ziegler-Natta catalyst in all stages. Preferably, znLLDPE-1 is prepared by using a slurry polymerization in at least one loop reactor and then a gas phase polymerization in a gas phase reactor.

[0292] The loop reactor-gas phase reactor system or loop-loop-gas phase reactor system is generally known as the Borealis technology. Reactor system.

[0293] In one embodiment, znLLDPE-1 is then preferably formed in a two-stage process comprising a slurry loop polymerization followed by a gas phase polymerization in the presence of a Ziegler-Natta catalyst.

[0294] Preferably, the lower molecular weight fraction (X-1) is produced in a continuously operated loop reactor where ethylene is polymerized in the presence of a Ziegler-Natta catalyst and then the higher molecular weight fraction (X-2) is formed in a gas phase reactor using the same Ziegler-Natta catalyst.

[0295] Such znLLDPE is well known in the prior art, for example described in WO 03 / 066698 or WO 2008 / 034630, or is commercially available, for example BorShape TM FX1001 and BorShape TM FX1002 (both from Borealis AG).

[0296] In another embodiment, znLLDPE-1 is preferably produced in a three-stage process, preferably comprising a first slurry reactor (loop reactor 1), wherein the first slurry loop reactor is connected in series with another slurry reactor (loop reactor 2); such that the first homopolymer fraction (LMW-1) produced in the loop reactor 1 is fed to the loop reactor 2, wherein a second homopolymer fraction (LMW-2) is produced in the presence of the first fraction (LMW-1). The loop reactor 2 is then connected in series to a gas phase reactor (GPR), such that the total low molecular weight fraction (X) leaving the second slurry reactor is fed to the GPR to produce znLLDPE-1. In this case, the reaction conditions in the two slurry reactors are selected such that the products produced in the two slurry reactors differ in terms of MFR and / or density.

[0297] This process is described in documents such as WO 2016 / 198273.

[0298] The Borstar PE 3G process is a suitable process.

[0299] Additionally, the znLLDPE-1 (preferably the znLLDPE-1 terpolymer) may contain one or more additives selected from antioxidants, processing stabilizers, slip agents, pigments, UV stabilizers and other additives known in the art.

[0300] Second multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2)

[0301] The mLLDPE-2 of the optional core layer (CL) is a multimodal metallocene-catalyzed linear low density polyethylene, different from the mLLDPE-1 defined in the seal layer (SL).

[0302] The density (ISO 1183) of the second multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) is between 905 and 930 kg / m 3 In the range of 910 to 925 kg / m 3 , more preferably 915 to 920 kg / m 3 .

[0303] The MFR2 (190°C, 2.16 kg, ISO 1133) of mLLDPE-2 is in the range of 0.01 to 1.5 g / 10 min, preferably 0.05 to 1.2 g / 10 min, more preferably 0.1 to 1.0 g / 10 min, even more preferably 0.2 to 0.8 g / 10 min.

[0304] In one embodiment, the melt flow ratio MFR of mLLDPE-2 is 21 / MFR2 is from 20 to 100, preferably from 25 to 80, more preferably from 30 to 60, even more preferably from 35 to 50.

[0305] The second multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) is a copolymer of ethylene and at least two different comonomers selected from α-olefins having 4 to 10 carbon atoms, such as 1-butene, 1-hexene, 1-octene, preferably 1-butene and 1-hexene.

[0306] In one embodiment, the second multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) of the core layer (CL) consists of

[0307] (i) 30.0 to 70.0 wt% of a polyethylene component (Y), and

[0308] (ii) 70.0 to 30.0 wt% of a polyethylene component (Z).

[0309] The total amount of (Y) and (Z) is 100.0 wt%.

[0310] In another embodiment of the present invention, the polyethylene component (Y) consists of ethylene polymer fractions (Y-1) and (Y-2).

[0311] It is possible to produce fraction (Y-1) first and then produce fraction (Y-2) in the presence of fraction (Y-1) in a subsequent reactor, or vice versa, i.e. produce fraction (Y-2) first and then produce fraction (Y-1) in the presence of fraction (Y-2) in a subsequent reactor. It is preferred to produce fraction (Y-1) first.

[0312] The multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) is referred to herein as "multimodal" because the polyethylene component (Y), optionally comprising ethylene polymer fractions (Y-1) and (Y-2), and the polyethylene component (B) are produced under different polymerization conditions, resulting in different melt flow rates (MFR, e.g. MFR2). That is, the multimodal polyethylene is multimodal at least with respect to the difference in MFR of the polyethylene components (Y) and (Z).

[0313] Preferably, the α-olefin comonomer having 4 to 10 carbon atoms of the polyethylene component (Y) is different from the α-olefin comonomer having 4 to 10 carbon atoms of the polyethylene component (Z); more preferably, the α-olefin comonomer having 4 to 10 carbon atoms of the polyethylene component (Y) is selected from 1-butene, 1-hexene and 1-octene, more preferably 1-butene; and the α-olefin monomer having 4 to 10 carbon atoms of the polyethylene component (Z) is preferably selected from 1-hexene and 1-octene, more preferably 1-hexene.

[0314] The comonomer type of polymer fractions (Y-1) and (Y-2) is the same, so fractions (Y-1) and (Y-2) use the same α-olefin comonomer having 4 to 10 carbon atoms, and more preferably both fractions use 1-butene as the comonomer.

[0315] Thus, in a preferred embodiment, the polyethylene component (Y) is an ethylene-1-butene polymer component (Y) and the polyethylene component (Z) is an ethylene-1-hexene polymer component (B).

[0316] The ethylene polymer components (Y) and (Z) differ in their MFR2.

[0317] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer component (Y) is in the range of 10.0 to 400 g / 10 min, preferably 30.0 to 350 g / 10 min, more preferably 50.0 to 300 g / 10 min, even more preferably 80.0 to 250 g / 10 min, still more preferably 100 to 200 g / 10 min, such as 120 to 160 g / 10 min.

[0318] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer component (Z) is in the range of 0.0001 to 1.0 g / 10 min, preferably 0.0005 to 0.5 g / 10 min, more preferably 0.001 to 0.1 g / 10 min, even more preferably 0.002 to 0.01 g / 10 min.

[0319] When the ethylene-1-butene polymer component (Y) consists of ethylene polymer fractions (Y-1) and (Y-2), the MFR2 of the ethylene polymer fractions (Y-1) and (Y-2) may be different or the same.

[0320] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer fraction (Y-1) is in the range of 5.0 to 800.0 g / 10 min, preferably 10.0 to 400.0 g / 10 min, more preferably 20.0 to 200.0 g / 10 min, even more preferably 25.0 to 150.0 g / 10 min, such as 30.0 to 100.0 g / 10 min.

[0321] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer fraction (Y-2) is in the range of 50 to 1000 g / 10 min, preferably 100 to 800 g / 10 min, more preferably 200 to 600 g / 10 min, most preferably 300 to 550 g / 10 min.

[0322] Preferably, the MFR2 of the ethylene polymer fraction (Y-2) is higher than the MFR2 of the ethylene polymer fraction (Y-1).

[0323] In one embodiment of the present invention, preferably, the ratio of the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene-1-butene polymer component (Y) to the MFR2 (190°C, 2.16 kg, ISO 1133) of the final multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) is at least 100 to 600, preferably 200 to 500, more preferably 300 to 400.

[0324] The density of the ethylene polymer component (Y) is in the range of 930 to 960 kg / m 3 In the range of 935 to 955 kg / m 3 , more preferably 940 to 950 kg / m 3 , and / or the density of the ethylene polymer component (Z) is from 885 to 910 kg / m 3 In the range of 890 to 905 kg / m 3 , more preferably 893 to 900 kg / m 3.

[0325] When the ethylene-1-butene polymer component (Y) consists of the ethylene polymer fractions (Y-1) and (Y-2), the densities of the ethylene polymer fractions (Y-1) and (Y-2) may be different or the same.

[0326] The density of the polymer fraction (Y-1) is between 930 and 960 kg / m 3 In the range of 935 to 955 kg / m 3 , more preferably 940 to 950 kg / m 3 .

[0327] The density of the polymer fraction (Y-2) is between 935 and 955 kg / m 3 In the range of 940 to 950 kg / m 3 .

[0328] Within the scope of the present invention, the first and second ethylene polymer fractions (Y-1 and Y-2) of the polyethylene component (Y) are present in a weight ratio of 4:1 to 1:4, such as 3:1 to 1:3, or 2:1 to 1:2, or 1:1.

[0329] The polyethylene component (Y) is present in an amount of 30.0 to 70.0 wt%, preferably 32.0 to 55.0 wt%, even more preferably 34.0 to 45.0 wt%, based on the multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2).

[0330] Therefore, the content of the polyethylene component (Z) is 70.0 to 30.0 wt%, preferably 68.0 to 45.0 wt%, more preferably 66.0 to 55.0 wt%, based on the multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2).

[0331] The multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) can be produced by the two-stage or three-stage polymerization process described for the first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1).

[0332] mLLDPE-2 is formed using a metallocene catalyst.

[0333] In another embodiment, mLLDPE-2 can also be produced in the presence of a metallocene complex of formula (I), as described in the section of mLLDPE-1.

[0334] mLLDPE-2 may optionally contain additives and / or fillers.

[0335] Optional additives and fillers and their amounts are conventional in the film application field. Examples of such additives are antioxidants, processing stabilizers, UV stabilizers, pigments, fillers, antistatic additives, antiblocking agents, nucleating agents, acid scavengers and polymer processing agents (PPA) and the like.

[0336] Multilayer film

[0337] The multilayer polyethylene film of the present invention comprises at least a layer (A) as a sealant layer (SL), and a layer (B) as a skin layer (SKL).

[0338] In one embodiment, the present invention provides a multilayer polyethylene film, comprising at least a layer (A) serving as the sealing layer (SL), a layer (B) serving as the surface layer (SKL), and a layer (C) serving as the core layer (CL), wherein the core layer (CL) is located between the sealing layer (SL) and the surface layer (SKL).

[0339] Preferably, the multilayer film according to the invention consists of layer (A) as sealing layer (SL), layer (B) as skin layer (SKL) and layer (C) as core layer (CL).

[0340] The core layer (CL) is sandwiched between the skin layer (SKL) and the sealing layer (SL). The core layer (CL) is preferably in direct contact with the skin layer (SKL). The core layer (CL) is preferably in direct contact with the sealing layer (SL). The core layer (CL) is preferably in direct contact with the sealing layer (SL) and the skin layer (SKL).

[0341] Therefore, the preferred membrane structure is SL / CL / SKL, that is, A / C / B.

[0342] The multilayer film of the present invention can be prepared using blown extrusion techniques well known in the art. Suitable blends of the desired components for each layer can be blended and coextruded. It should be understood that any layer of the film of the present invention may also contain standard polymer additives if desired.

[0343] The thickness of the multilayer film of the present invention may be from 20 to 120 μm, preferably from 30 to 100 μm, more preferably from 40 to 80 μm. The film of the present invention is preferably not stretched in the longitudinal or transverse or biaxial directions.

[0344] For a three-layer structure, the thicknesses of the sealing layer (SL), skin layer (SKL), and core layer (CL) may be equal, or the core layer (CL) may be thicker than the skin layer (SKL) and sealing layer (SL).

[0345] A convenient film comprises a skin layer (SKL) and a sealing layer (SL), wherein the skin layer (SKL) and the sealing layer (SL) each account for 10.0 to 35.0%, preferably 15.0 to 30.0%, and more preferably 18.0 to 25.0% of the final total thickness of the three-layer film, and the core layer (CL) accounts for the remaining thickness, for example, 30.0 to 80.0%, preferably 40.0 to 70.0%, and more preferably 50.0 to 64.0% of the final total thickness of the three-layer film.

[0346] The total thickness of the film is 100%, so the sum of the individual layers must be 100%.

[0347] The film of the present invention is characterized in that it has a hot tack (maximum hot tack) of at least 5.8 N or more when measured according to ASTM F 1921-98 (2004) Method B on a three-layer blown film sample (thickness 60 μm).

[0348] Preferably, the hot tack force (HTF) is in the range of 5.8N to 15.0N, more preferably in the range of 6.6N to 12.0N, even more preferably in the range of 7.5N to 10.0N.

[0349] In an embodiment of the present invention, the multilayer film has a hot tack temperature (HTT) of less than 87°C when measured according to ASTM F 1921-98 Method B on a three-layer blown film sample (thickness 60 μm).

[0350] Preferably, the hot tack temperature (HTT) is in the range of 65 to 86°C, more preferably in the range of 68 to 85°C, even more preferably in the range of 70 to 82°C.

[0351] The film of the present invention may have a sealing initiation temperature (SIT) of less than 86°C, preferably in the range of 60 to 85°C, more preferably in the range of 62 to 84°C, even more preferably in the range of 65 to 80°C, as determined on a three-layer blown film with a thickness of 60 μm as described in the experimental part.

[0352] In another embodiment, the film of the present invention is further characterized in that the dart drop impact strength (DDI) measured on a 60 μm three-layer test blown film according to ISO 7765-1:1988 standard is at least 200g to 1000g, preferably 250g to 800g, and more preferably 300g to 600g.

[0353] According to ASTM D1003 standard, the haze of the film of the present invention measured on a 60 μm three-layer test blown film can be less than 50%, preferably in the range of 5% to 48%, more preferably 10% to 45%, and even more preferably 15% to 41% or less.

[0354] In another embodiment, the multilayer film according to the invention is characterized by at least the following properties:

[0355] a) a hot tack force (maximum hot tack force (HTF)) measured on a three-layer blown film sample (thickness 60 μm) according to ASTM F 1921-98 (2004) Method B is in the range of 5.8 N to 15.0 N, more preferably in the range of 6.6 to 12.0 N, even more preferably in the range of 7.5 to 10.0 N, and

[0356] b) a hot stick temperature (HTT) measured on a three-layer blown film sample (thickness 60 μm) according to ASTM F 1921-98 Method B is lower than 90°C, and is in the range of 65 to 86°C, more preferably in the range of 68 to 85°C, and more preferably in the range of 70 to 82°C; and

[0357] c) The haze measured on a 60 μm three-layer test blown film according to ASTM D1003 is in the range of 5% to 48%, more preferably 10% to 45%, even more preferably 15% to 41% or less.

[0358] In another embodiment, the multilayer film according to the present invention satisfies the inequality (I) (SIT+HTT) / HTF<23, preferably <22, and more preferably <21, wherein SIT is the seal initiation temperature determined on the three-layer blown film with a thickness of 60 μm as described in the experimental part, HTT is the hot tack temperature measured on the three-layer test blown film sample with a thickness of 60 μm according to ASTM F 1921-98 Method B, and HTF is the hot tack force measured on the three-layer test blown film sample with a thickness of 60 μm according to ASTM F 1921-98 (2004) Method B.

[0359] The multilayer film of the present invention is fully recyclable, thus improving sustainability, as it is a "100% PE" solution, containing no other polymers besides vinyl polymers.

[0360] The multilayer films according to the present invention are very suitable for use in various packaging applications, among which applications related to food packaging are preferred.

[0361] The invention will be further described with reference to the following non-limiting examples. DETAILED DESCRIPTION

[0362] Determination method

[0363] Unless otherwise stated in the description or in the experimental part, the properties of the polymers (including their fractions and components) were determined and / or their samples were prepared using the following methods, as described in the text or in the experimental part.

[0364] Melt flow rate

[0365] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR is an indication of the flowability of the polymer and therefore of its processability. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR of polyethylene is determined at 190°C. The MFR can be determined at different loads, such as 2.16 kg (MFR2), 5 kg (MFR5) or 21.6 kg (MFR 21 ).

[0366] Calculation of MFR2 in mLLDPE-1 of component B and fraction (A-2)

[0367] logA=x·logB+(1-x)·logC

[0368]

[0369] For component B:

[0370] B = MFR2 of component (A)

[0371] C = MFR2 of component (B)

[0372] A = Final MFR2 of the multimodal polyethylene copolymer (P) (blend)

[0373] X = weight fraction of component (A)

[0374] For fraction (A-2):

[0375] B = MFR2 of the first fraction (A-1)

[0376] C = MFR2 of the second fraction (A-2)

[0377] A = Final MFR2 of the polymer (= component (A)) of the recycling process (mixture)

[0378] X = weight fraction of the first fraction (A-1)

[0379] The above formula also applies to the components and fractions of HDPE, znLLDPE-1 and mLLDPE-2.

[0380] density

[0381] The density of the polymer is measured according to ISO 1183 on compression molded test specimens prepared according to EN ISO 1872-2 (February 2007) and is expressed in kg / m 3 .

[0382] DSC analysis, melting temperature (Tm)

[0383] Data were measured on 5 to 7 mg samples using a TA Instruments Q2000 Differential Scanning Calorimeter (DSC). The DSC was run according to ISO 11357 / Part 3 / Method C2 over a temperature range of -30 to +225°C with a heating / cooling / heating cycle at a scan rate of 10°C / min.

[0384] Crystallization temperature (T c ) and crystallization enthalpy (H c ) is determined by the cooling step, the melting temperature (T m ) and melting enthalpy (H m ) is determined by the second heating step.

[0385] Comonomer content:

[0386] Quantitative analysis of microstructure using NMR spectroscopy

[0387] Quantitative nuclear magnetic resonance (NMR) technology was used to quantitatively analyze the comonomer content of the polymer.

[0388] In the molten state, the NMR spectrometer was used to record the ions at 500.13 and 125.76 MHz. 1 H and 13 Quantification of C 13 C{1H}NMR spectra. All spectra were obtained using 13 A C-optimized 7 mm magic angle spinning (MAS) probe was recorded at 150 °C, with nitrogen used for all pneumatics. Approximately 200 mm of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at 4 kHz. This setup was chosen primarily to achieve the high sensitivity required for rapid identification and accurate quantification. {klimke06,parkinson07,castignolles09}. Standard single pulse excitation was used, with NOEs with short recycle delays {pollard04,klimke06} and an RS-HEPT decoupling scheme {fillip05,griffin07}. A total of 1024 (1k) transients were acquired for each spectrum.

[0389] Quantification 13 C{ 1 H} NMR spectra were processed and integrated, and relevant quantitative properties were determined from the integration. All chemical shifts were internally referenced to the methylene signal (δ+) at 30.00 ppm.

[0390] The ethylene content is quantified by the integration of the methylene (δ+) sites at 30.00 ppm over the number of reported sites for each monomer:

[0391] E=Iδ+ / 2

[0392] Correction for the presence of isolated comonomer is made based on the amount of isolated comonomer present:

[0393] E total = E + (3*B + 2*H) / 2

[0394] where B and H are for their respective comonomers. If there is continuous and discontinuous comonomer incorporation, corrections are made in a similar manner.

[0395] Characteristic signals corresponding to 1-butene incorporation were observed, and the comonomer fraction was calculated as the fraction of 1-butene in the polymer relative to all monomers in the polymer:

[0396] fBtotal=(Btotal / (Etotal+Btotal+Htotal)

[0397] The content of isolated 1-butene in the EEBEE sequence is determined by the 38.3 ppm * The integral of the B2 site was quantified as a percentage of the number of reported sites per comonomer.

[0398] B=I *B2

[0399] The content of continuously incorporated 1-butene in the EEBBEE sequence was quantified by the integration of the ααB2B2 sites at 39.4 ppm over the number of reported sites per comonomer.

[0400] BB=2*IααB2B2

[0401] The amount of discontinuously incorporated 1-butene in the EEBEBEE sequence was quantified by the integration of the ββB2B2 sites at 24.7 ppm over the number of reported sites per comonomer.

[0402] BEB=2*IββB2B2

[0403] Since isolated incorporation (EEBEE) and discontinuous incorporation (EEBEBEE) of 1-butene are * B2 and * The βB2B2 sites overlap, so a correction for the total amount of isolated incorporated 1-butene was made based on the amount of discontinuous 1-butene.

[0404] B=I *B2 -2*I ββB2B2

[0405] The total 1-butene content was calculated from the sum of isolated, continuously and discontinuously incorporated 1-butene.

[0406] Total B=B+BB+BEB

[0407] The total mole fraction of 1-butene in the polymer is calculated as:

[0408] fB=(Total B / (Total E+Total B+Total H)

[0409] Characteristic signals corresponding to 1-hexene incorporation were observed, and the comonomer fraction was calculated as the fraction of 1-hexene in the polymer relative to all monomers in the polymer:

[0410] fHtotal=(Htotal / (Etotal+Btotal+Htotal)

[0411] The content of isolated 1-hexene in the EEHEE sequence is determined by * The integral of the B4 site was quantified as a percentage of the number of reported sites per comonomer.

[0412] H=I *B4

[0413] The amount of 1-hexene continuously incorporated in the EEHHEE sequence was quantified by the integration of the ααB4B4 sites at 40.5 ppm over the number of reported sites per comonomer.

[0414] HH=2*IααB4B4

[0415] The amount of discontinuously incorporated 1-hexene in the EEHEHEE sequence was quantified by the integration of the ββB4B4 sites at 24.7 ppm over the number of reported sites per comonomer.

[0416] HEH=2*IββB4B4

[0417] The total mole fraction of 1-hexene in the polymer is calculated as:

[0418] fH=(H total / (E total+B total+H total)

[0419] The mole percentage of comonomer incorporation is calculated from the mole fraction:

[0420] B[mol%]=100*fB

[0421] H[mol%]=100*fH

[0422] The weight percent of comonomer incorporation is calculated from the mole fraction:

[0423] B[wt%]=100*(fB*56.11) / ((fB*56.11)+(fH*84.16)+((1-(fB+fH))*28.05))

[0424] H [wt%] = 100 * (fH * 84.16) / ((fB * 56.11) + (fH * 84.16) + ((1 - (fB + fH)) * 28.05)).

[0425] References:

[0426] Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, H.W., Wilhelm, M., Macromol. Chem. Phys. 2006; 207: 382.

[0427] Parkinson, M., Klimke, K., Spiess, H.W., Wilhelm, M., Macromol. Chem. Phys. 2007; 208: 2128.

[0428] Pollard, M., Klimke, K., Graf, R., Spiess, H.W., Wilhelm, M., Sperber, O., Piel, C., Kaminsky, W., Macromolecules 2004; 37: 813.

[0429] Filip, X., Tripon, C., Filip, C., J. Mag. Resn. 2005, 176, 239

[0430] Griffin, J.M., Tripon, C., Samoson, A., Filip, C., and Brown, S.P., Mag. Res. in Chem. 2007 45, S1, S198

[0431] Castignolles, P., Graf, R., Parkinson, M., Wilhelm, M., Gaborieau, M., Polymer 50 (2009) 2373

[0432] Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443

[0433] Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, A.L., Macromoleucles 30 (1997) 6251

[0434] Zhou,Z.,Kuemmerle,R.,Qiu,X.,Redwine,D.,Cong,R.,Taha,A.,Baugh,D.Winniford,B.,J.Mag.Reson.187(2007)225

[0435] Busico,V.,Carbonniere,P.,Cipullo,R.,Pellecchia,R.,Severn,J.,Talarico,G.,Macromol.Rapid Commun.2007,28,1128

[0436] Resconi,L.,Cavallo,L.,Fait,A.,Pimontesi,F.,Chem.Rev.2000,100,1253

[0437] Sealing start temperature (SIT); Sealing end temperature (SET), Sealing range:

[0438] The method can determine the sealing temperature range (sealing range) of polyethylene films, in particular blown films or cast films. The sealing temperature range is the temperature range within which the film can seal films under the following conditions.

[0439] The lower limit (seal initiation temperature (SIT)) is the sealing temperature at which a seal strength of 5 N is achieved. The upper limit (seal end temperature (SET)) is reached when the film sticks to the sealing device.

[0440] The measurements were carried out according to a slightly modified ASTM F1921-12, where the test parameters such as sealing pressure, cooling time and test speed were modified. The force / temperature curve was measured until the film failed thermally. The sealing range was determined on a J&B 4000 universal sealer with three-layer test blown film with a thickness of 60 μm, with the following further parameters:

[0441] Adjustment time: >96 hours

[0442] Sample width: 25mm

[0443] Sealing pressure: 0.4N / mm 2 (Polyethylene)

[0444] Sealing time: 1 second

[0445] Delay time: 30 seconds

[0446] Sealing clip size: 50x5 mm

[0447] Sealing clip shape: flat

[0448] Sealing coating: Niptef

[0449] Sealing temperature: ambient temperature -240℃

[0450] Sealing temperature interval: 5°C

[0451] Starting temperature: 50°C Grip separation rate: 42mm / sec

[0452] Hot tack temperature (lowest temperature at which maximum hot tack is obtained) and hot tack force (maximum hot tack force) are measured according to ASTM F1921 Method B on three-layer blown films with a thickness of 60 μm using the following settings:

[0453] Q-name Instruments: Hot Tack-Seal Tester

[0454] Model: J&B model 4000MB

[0455] Sealing strip length: 50[mm]

[0456] Sealing strip width: 5[mm]

[0457] Sealing strip shape: flat

[0458] Sealing pressure: 0.15N / mm 2

[0459] Sealing time: 1 second

[0460] Sealing strip coating:

[0461] Roughness of coated sealing strip: 1[μm]

[0462] Film sample width: 25mm

[0463] Cooldown: 0.2 seconds

[0464] Peeling speed: 200mm / s

[0465] Starting temperature: 50℃

[0466] End temperature: burn-through and / or shrinkage

[0467] Temperature increment: 5°C

[0468] All film test specimens are prepared in a standard atmosphere for conditioning and testing at 23°C ± 2°C) and 50% (± 10%) relative humidity. The minimum conditioning time for the test specimens in the standard atmosphere is at least 40 hours before the start of testing. The minimum storage time between extrusion of the film sample and the start of testing is at least 88 hours. The hot tack test measures the strength of the heat seal formed after the film is sealed and before it is cooled to ambient temperature.

[0469] Hot tack is measured as a function of temperature within the temperature range and temperature increments described above. The number of test specimens at each temperature is at least 3. Hot tack is evaluated as the maximum force (maximum peak value) when the failure mode is "peel".

[0470] Dart Drop Impact Strength (DDI): Determination of impact resistance by free falling dart method

[0471] DDI is measured from produced films (non-oriented films and laminates) according to ISO 7765-1:1988 / Method A. This test method is used to determine the energy required for a free-falling dart to strike a film from a specified height under specified conditions to cause 50% of the tested specimens to fail (Step Method A). During the test, the same incremental drop mass is used and after each specimen is tested, the drop mass is reduced or increased by the same increment depending on the observed result (failure or non-failure) of the specimen.

[0472] Standard conditions:

[0473] Adjustment time: >96 hours

[0474] Test temperature: 23℃

[0475] Dart head material: phenolic

[0476] Dart diameter: 38mm

[0477] Lowering height: 660mm

[0478] result:

[0479] Impact failure weight - 50% [g]

[0480] Haze

[0481] Haze was measured according to ASTM D 1003-00 on a three-layer film having a thickness of 60 μm as shown below.

[0482] Membrane sample preparation

[0483] The three-layer test film consisting of layers A, B and C and the three-layer comparative film each having a thickness of 60 μm were produced on a Dr. Colin three-layer blown film production line.

[0484] The melt temperature was fixed at 210° C. The output of the extruder amounted to 10 kg / h.

[0485] Other parameters of the blown film production line are: die gap: 1.5mm; die size: 60mm; blow-up ratio (BUR): 1:2.5; frost line height: 120mm

[0486] Example:

[0487] Materials used:

[0488] • Multimodal Ziegler-Natta catalyzed linear low density polyethylene (znLLDPE-1) for layers (C) of IE1 to IE4 and layer (B) of CE1:

[0489] FX1001: multimodal α-olefin terpolymer, purchased from Borealis AG, density 931 kg / m 3 , MFR5 (190℃ / 5kg) is 0.9g / 10min, Tm is 127℃; produced using Ziegler-Natta catalyst. It contains antioxidant.

[0490] Multimodal metallocene-catalyzed linear low density polyethylene for Comparative Example CE2 Layer A:

[0491] AnteoTM FK1820: Bimodal ethylene / 1-butene / 1-hexene terpolymer, density 918

[0492] kg / m 3 , MFR2 (190°C / 2.16kg) is 1.5 g / 10 min, Tm is 122°C, produced using a metallocene catalyst; purchased from Borouge. It contains antioxidants and processing aids.

[0493] Multimodal high density polyethylene (HDPE) for layer (B):

[0494] HDPE made of Borouge FB5600, FB5600 is a bimodal ethylene copolymer with a density of 960kg / m 3 , Tm is 132℃, MFR2 is 0.7g / 10min, MFR5 is

[0495] 2.5g / 10min, MFR 21 42g / 10min, MFR 21 / MFR5 is 16.8.

[0496] Preparation of multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) for layer A of the multilayer film of the present invention

[0497] Catalyst Example: Catalyst Preparation of CAT1

[0498] SiO2 loading:

[0499] 10 kg of silica (PQ Corporation ES757, calcined at 600°C) was added from a feed bucket and inerted in the reactor until the oxygen content dropped below 2 ppm.

[0500] Preparation of MAO / tol / MC:

[0501] A 30 wt% MAO toluene solution (14.1 kg) was added from a balance to another reactor, followed by the addition of toluene (4.0 kg) at 25°C (oil circulation temperature) and stirring at 95 rpm. After the addition of toluene, the stirring speed was increased from 95 rpm to >200 rpm for 30 minutes. 477 g of metallocene Rac-dimethylsilanediylbis{2-(5-(trimethylsilyl)furan-2-yl)-4,5-dimethylcyclopentadiene-1-yl}zirconium dichloride was added from a metal cylinder and then rinsed with 4 kg of toluene (total amount of toluene was 8.0 kg). When methylcyclohexane (MC) was fed, the reactor stirring speed was changed to 95 rpm, and after 3 hours of reaction, the stirring speed was restored to 200 rpm. After the reaction time, the MAO / tol / MC solution was transferred to the feed container.

[0502] Preparation of catalyst:

[0503] During the addition of MAO / tol / MC, the reactor temperature was set at 10°C (oil circulation temperature) and the stirring speed was 40 rpm. The MAO / tol / MC solution (22.2 kg) was added over 205 minutes and then stirred for 60 minutes (the oil circulation temperature was set at 25°C). After stirring, the "dry mixture" was stabilized at 25°C (oil circulation temperature) for 12 hours with a stirring speed of 0 rpm. The reactor was rotated 20° (back and forth) with a stirring speed of 5 rpm and stirred several times per hour.

[0504] After stabilization, the catalyst was dried at 60 degrees Celsius (oil circulation temperature) with a nitrogen flow rate of 2 kg / h for 2 hours, and then dried under vacuum conditions for 13 hours (same nitrogen flow rate, stirring speed of 5 rpm). The dried catalyst was sampled and the HC content was determined by thermogravimetric method in a glove box using a Sartorius moisture analyzer (model MA45). The target HC level was less than 2% (actual 1.3%).

[0505] polymerization:

[0506] A Borstar pilot plant with a three-reactor configuration (loop 1 - loop 2 - gas phase reactor 1) and a prepolymerization loop reactor was used.

[0507] Using the polymerization conditions given in Table 1, mLLDPE-1-A for IE1 to IE3 and CE1, and mLLDPE-1-B for IE4 were produced.

[0508] Table 1: Polymerization conditions of mLLDPE-1-A and mLLDPE-1-B

[0509]

[0510]

[0511] The polymer was mixed with 2400 ppm of Irganox B561 (available from BASF SE) and 270 ppm of Dynamar FX 5922 (available from 3M) and extruded into pellets using a JSW extruder under nitrogen atmosphere to give an SEI of 230 kWh / kg and a melt temperature of 250°C.

[0512] Table 2: Properties of mLLDPE-1-A, mLLDPE-1-B and comparative mmLLDPE FK1820

[0513]

[0514]

[0515] Preparation of multimodal high density polyethylene (HDPE) for layer B of the multilayer film of the present invention:

[0516] Catalyst Example: Catalyst Preparation of CAT2 for IE1

[0517] 130 g of the metallocene complex bis(1-methyl-3-n-butylcyclopentadienyl)zirconium dichloride (IV) (CAS No. 151840-68-5) and 9.67 kg of a 30% commercial methylaluminoxane (MAO) toluene solution were mixed, and then 3.18 kg of dried purified toluene was added. The resulting complex solution was slowly and evenly sprayed on 17 kg of a silica carrier Sylopol 55SJ (provided by Grace) for 2 hours. The temperature was maintained below 30° C. The complex was added at 30° C. and the mixture was reacted for 3 hours.

[0518] Catalyst Example: Catalyst preparation of CAT1 for IE2 is as above (as described in the section of mLLDPE-1)

[0519] polymerization:

[0520] A Borstar pilot plant with a three-reactor configuration (loop 1 - loop 2 - gas phase reactor 1) and a prepolymerization loop reactor was used.

[0521] Using the polymerization conditions given in Table 3, HDPE-A for IE1 and HDPE-B for IE2 were produced.

[0522] Table 3: Polymerization conditions of HDPE-A and HDPE-B

[0523]

[0524]

[0525] The polymer was mixed with 2400 ppm of Irganox B561 (available from BASF SE) and 270 ppm of Dynamar FX 5922 (available from 3M) and extruded into pellets using a JSW extruder under nitrogen atmosphere to give an SEI of 230 kWh / kg and a melt temperature of 250°C.

[0526] Table 4: Material properties of HDPE-1 and HDPE-2

[0527]

[0528]

[0529] Preparation of multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) for layer C of the multilayer film of the present invention

[0530] Catalyst Example: Catalyst preparation of CAT1 is as described above (as described in the section of mLLDPE-1)

[0531] polymerization:

[0532] A Borstar pilot plant with a three-reactor configuration (loop 1 - loop 2 - gas phase reactor 1) and a prepolymerization loop reactor was used.

[0533] Using the polymerization conditions given in Table 5, mLLDPE-2 was produced.

[0534] Table 5: Polymerization conditions of mLLDPE-2

[0535]

[0536]

[0537]

[0538] The polymer was mixed with 2400 ppm of Irganox B561 (available from BASF SE) and 270 ppm of Dynamar FX 5922 (available from 3M) and extruded into pellets using a JSW extruder under nitrogen atmosphere to give an SEI of 230 kWh / kg and a melt temperature of 250°C.

[0539] Table 6: Material properties of mLLDPE-2

[0540]

[0541] Three-layer film

[0542] The following three-layer membrane structure was prepared using the above method (Membrane Sample Preparation).

[0543] Table 7: Film structures of the present invention and comparison

[0544]

[0545]

[0546] * wt% based on each layer (SKL or CL or SL)

[0547] Table 8: Film structures of the present invention and comparison

[0548]

[0549] ** wt% based on overall three-layer film

[0550] Table 9 shows the membrane properties of the inventive and comparative membrane structures.

[0551] Table 9: Membrane properties

[0552]

[0553] The data show that if the sealant layer (SL) is the same, i.e. IE1-IE3 and CE1, and is used in combination with the HDPE for the skin layer (SKL) as described in the present invention, then in this case the HTF of the inventive examples IE1-IE3 is significantly higher than that of CE1. In addition, the haze of IE1-IE3 is significantly lower than that of CE1, despite the much lower density of the skin layer of CE1.

[0554] If the skin layers (SKL) are the same, i.e. IE4 and CE2, but the mLLDPE-1 in the sealing layer (SL) is different (i.e. mLLDPE-1 and FK1820), then in this case, their optical parameters (i.e. haze) are comparable, but IE4 has higher dart impact strength and HTF than CE2.

[0555] In general, the multilayer film having the skin layer (SKL) and the sealing layer (SL) designed according to the specific polymers of the present invention (i.e., a specific HDPE in the skin layer and a specific mLLDPE-1 in the sealing layer (SL)) can improve the overall sealing performance, as shown by (SIT+HTT) / HTF being lower than 23, compared with those comparative examples in which the polymer in the skin layer (SKL) or the sealing layer (SL) is different from the polymer described in the film of the present invention.

Claims

1. A multilayer polyethylene film comprising at least a layer (A) as a seal layer (SL), and a layer (B) as a skin layer (SKL); in, The sealing layer (SL) comprises: i) 30.0 wt% to 100.0 wt% of a first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1), based on the total weight of the sealing layer (SL), having the following properties Density 905 to 930 kg / m 3 within the range (ISO 1183); MFR2 (190°C, 2.16kg, ISO 1133) in the range of 0.1 to 2.0 g / 10 min; MFR 21 The ratio of MFR (190°C, 21.6 kg, ISO 1133) to MFR2 (190°C, 2.16 kg, ISO 1133), i.e. MFR 21 / MFR2, in the range of 22 to 70; Wherein, the first multimodal metallocene-catalyzed linear low-density polyethylene (mLLDPE-1) is composed of the following parts (i) 30.0 to 70.0 wt% of a polyethylene component (A) consisting of ethylene polymer fractions (A-1) and (A-2); and (ii) 70.0 to 30.0 wt% of a polyethylene component (B), The total amount of (A) and (B) is 100.0 wt%, and ii) 0.0 wt% to 70.0 wt% of ethylene-1-octene or ethylene-1-butene plastomer having the following characteristics Density 860 to 910 kg / m 3 range (ISO 1183), and MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.5 to 10.0 g / 10 min; and Wherein, the surface layer (SKL) comprises: 60.0wt% to 100.0wt% of high density polyethylene (HDPE) based on the total weight of the skin layer (SKL) with a density of 945 to 970kg / m 3 range (ISO 1183).

2. The multilayer polyethylene film according to claim 1, wherein The multilayer polyethylene film comprises at least a layer (A) as a sealing layer (SL), a layer (B) as a skin layer (SKL), and a layer (C) as a core layer (CL), wherein the core layer (CL) is located between the sealing layer (SL) and the skin layer (SKL), wherein the core layer comprises: x) 50.0 wt% to 99.0 wt% of a multimodal Ziegler-Natta catalyzed linear low density polyethylene (znLLDPE-1) having a density (ISO 1183) in the range of 920 to 950 kg / m 3 MFR5 (190°C, 5kg, ISO 1133) is in the range of 0.1 to 4.0 g / 10 min; and y) from 1.0 wt% to 50.0 wt%, based on the total weight of the core layer (CL), of a second multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) having the following properties Density 905 to 930 kg / m 3 within the range of (ISO 1183); and MFR2 (190°C, 2.16kg, ISO 1133) in the range of 0.1 to 2.0 g / 10 min; The sum of x)+y) is 100 wt%.

3. The multilayer polyethylene film of claim 1 or 2, wherein the first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) of layer (A), i.e. the sealing layer (SL), consists of: (i) 30.0 to 70.0 wt% of a polyethylene component (A) which is an ethylene-1-butene component (A), and (ii) 70.0 to 30.0 wt% of a polyethylene component (B), which is an ethylene-1-hexene component (B), the total amount of (A) and (B) being 100.0 wt%, wherein The ethylene-1-butene component (A) has the following characteristics MFR2 (190°C, 2.16 kg, ISO 1133) is in the range of 2.0 to 400 g / 10 min, preferably 2.5 to 300 g / 10 min, more preferably 3.0 to 200 g / 10 min, even more preferably 3.2 to 100 g / 10 min, still more preferably 3.5 to 70.0 g / 10 min, and / or Density (ISO 1183) 920 to 950 kg / m 3 In the range of 925 to 948 kg / m 3 , more preferably 930 to 945 kg / m 3 , and / or The ethylene-1-hexene component (B) has the following characteristics MFR2 (190°C, 2.16 kg, ISO 1133) is in the range of 0.001 to 1.5 g / 10 min, preferably 0.005 to 1.0 g / 10 min, more preferably 0.01 to 0.8 g / 10 min, even more preferably 0.02 to 0.5 g / 10 min, and / or Density (ISO 1183) 885 to 918 kg / m 3 In the range of 888 to 915 kg / m 3 , and more preferably 890 to 912 kg / m 3 .

4. The multilayer polyethylene film according to claim 3, wherein The ratio of MFR2 (190°C, 2.16 kg, ISO 1133) of the polyethylene component (A), preferably the ethylene-1-butene polymer component (A), of the first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) of layer (A), i.e. the sealing layer (SL), to the MFR2 (190°C, 2.16 kg, ISO 1133) of the final multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) is at least 3.0 to 120.0, preferably 3.5 to 100.0, more preferably 4.0 to 90.

0.

5. The multilayer polyethylene film according to claim 3 or 4, wherein: The ethylene-1-butene polymer component (A) of the first multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-1) of layer (A), i.e. the sealant layer (SL), consists of ethylene polymer fractions (A-1) and (A-2), wherein The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer fraction (A-1) is in the range of 1.0 to 800.0 g / 10 min, preferably 1.5 to 400.0 g / 10 min, more preferably 1.8 to 200.0 g / 10 min, even more preferably 2.0 to 50.0 g / 10 min, such as 2.1 to 40.0 g / 10 min, and / or Density (ISO 1183) 920 to 950 kg / m 3 In the range of 925 to 948 kg / m 3 , more preferably 930 to 946 kg / m 3 , and / or The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer fraction (A-2) is in the range of 2.0 to 400.0 g / 10 min, preferably 2.5 to 200.0 g / 10 min, more preferably 3.0 to 100.0 g / 10 min, most preferably 3.5 to 80.0 g / 10 min, and / or Density (ISO 1183) 920 to 950 kg / m 3 In the range of 920 to 945 kg / m 3 .

6. The multilayer polyethylene film according to any one of claims 1 to 5, wherein The high-density polyethylene (HDPE) of layer (B) or the surface layer (SKL) has the following characteristics: MFR2 (190°C, 2.16 kg, ISO 1133) is in the range of 0.1 to 3.0, preferably 0.2 to 2.5 g / 10 min, more preferably 0.5 to 2.0 g / 10 min, and / or MFR5 (190°C, 5kg, ISO 1133) is in the range of 1.0 to 10.0 g / 10 min, preferably 1.5 to 8.0 g / 10 min, more preferably 2.0 to 6.0 g / 10 min, and / or MFR 21 (190°C, 21.6 kg, ISO 1133) in the range of 20.0 to 100.0 g / 10 min, preferably 25.0 to 80.0 g / 10 min, more preferably 30.0 to 60.0 g / 10 min, and / or (Melt) flow rate ratio FRR21 / 5 (MFR 21 / MFR5) is 5 to 30, preferably 7 to 25, most preferably 8 to 20.

7. The multilayer polyethylene film according to any one of claims 1 to 6, wherein The high density polyethylene (HDPE) of layer (B), i.e. the skin layer (SKL), is a trimodal HDPE produced in the presence of a metallocene or Ziegler-Natta catalyst system, preferably in the presence of a metallocene catalyst system, and consists of a polyethylene component (D) and a polyethylene component (E), wherein The polyethylene component (D) is an ethylene copolymer, preferably an ethylene-1-butene copolymer, which has the following characteristics: MFR2 (190°C, 2.16 kg, ISO 1133) is in the range of 10 to 400 g / 10 min, preferably 12 to 200 g / 10 min, more preferably 15 to 100 g / 10 min, most preferably 20 to 50 g / 10 min, and Density (ISO 1183) 955 to 970 kg / m 3 In the range of 958 to 968 kg / m 3 , even more preferably 960 to 965 kg / m 3 ,and It consists of a first ethylene copolymer fraction (D-1) and a second ethylene copolymer fraction (D-2), wherein The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer fraction (D-1) and / or the ethylene polymer fraction (D-2) is preferably in the range of 10.0 to 80.0 g / 10 min, preferably 15.0 to 70.0 g / 10 min, more preferably 20.0 to 60.0 g / 10 min, even more preferably 30.0 to 50.0 g / 10 min; wherein the MFR2 of fraction (D-1) is preferably higher than the MFR2 of fraction (D-2), and The density (ISO 1183) of the ethylene polymer fraction (D-1) and / or (D-2) is preferably in the range of 945 to 975 kg / m 3 In the range of 950 to 970 kg / m 3 , even more preferably 952 to 968 kg / m 3 , wherein the density of fraction (D-2) is preferably higher than the density of fraction (D-1); and The polyethylene component (E) is an ethylene homopolymer or an ethylene copolymer, and its MFR2 (190°C, 2.16 kg, ISO 1133) is in the range of 0.01 to 1.0 g / 10 min, preferably 0.02 to 0.8 g / 10 min, more preferably 0.05 to 0.5 g / 10 min, and The density (ISO 1183) of the polyethylene component (E) is between 925 and 965 kg / m 3 In the range of 930 to 962 kg / m 3 , and more preferably 935 to 960 kg / m 3 ,in If the polyethylene component (E) is an ethylene copolymer, it is preferably an ethylene-1-hexene copolymer.

8. The multilayer polyethylene film according to any one of claims 1 to 6, wherein The high density polyethylene (HDPE) of layer (B), i.e. the surface layer, is a bimodal HDPE produced in the presence of a metallocene or Ziegler-Natta catalyst system, preferably a Ziegler-Natta catalyst system, and is composed of a lower molecular weight (LMW) polyethylene component (D) and a higher molecular weight (HMW) polyethylene component (E); wherein the lower molecular weight (LMW) polyethylene component (D) is an ethylene homopolymer with a density (ISO1183) of 965 to 975 kg / m 3 The higher molecular weight (HMW) polyethylene component (E) is an ethylene copolymer of ethylene and at least one C4 to C12 α-olefin, with a density (ISO 1183) of 935 to 955 kg / m 3 .

9. The multilayer polyethylene film according to any one of claims 2 to 8, wherein The density (ISO 1183) of the multimodal Ziegler-Natta catalyzed linear low density polyethylene (znLLDPE-1) of layer (C) or the core layer is between 925 and 945 kg / m 3 In the range of 928 to 942 kg / m 3 , more preferably 930 to 940 kg / m 3 ,and MFR5 (190°C, 5kg, ISO 1133) is in the range of 0.5 to 3.5 g / 10 min, preferably 0.7 to 3.0 g / 10 min, more preferably 0.8 to 2.5 g / 10 min, and it comprises (X-1) a relatively low molecular weight (LMW) ethylene homopolymer and (X-2) Higher molecular weight (HMW) terpolymer of ethylene, 1-butene and 1-hexene.

10. The multilayer polyethylene film according to any one of the preceding claims 2 to 9, wherein the multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) of layer (C), i.e. the core layer (CL), consists of: (i) 30.0 to 70.0 wt% of a polyethylene component (Y), preferably an ethylene-1-butene polymer component (Y), and (ii) 70.0 to 30.0 wt% of a polyethylene component (Z), preferably an ethylene-1-hexene polymer component (Z), wherein The total amount of (Y) and (Z) is 100.0 wt%, and The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer component (Y) is in the range of 10.0 to 400 g / 10 min, preferably 30.0 to 350 g / 10 min, more preferably 50.0 to 300 g / 10 min, even more preferably 80.0 to 250 g / 10 min, still more preferably 100 to 200 g / 10 min, such as 120 to 160 g / 10 min, and Density 930 to 960 kg / m 3 In the range of 935 to 955 kg / m 3 , more preferably 940 to 950 kg / m 3 , and among them The polyethylene component (Y) preferably consists of ethylene polymer fractions (Y-1) and (Y-2), The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer component (Z) is in the range of 0.0001 to 1.0 g / 10 min, preferably 0.0005 to 0.5 g / 10 min, more preferably 0.001 to 0.1 g / 10 min, even more preferably 0.002 to 0.01 g / 10 min, and Density 885 to 910 kg / m 3 In the range of 890 to 905 kg / m 3 , more preferably 893 to 900 kg / m 3 ; and / or Wherein, the ratio of MFR2 (190 ℃, 2.16 kg, ISO1133) of the polyethylene component (Y), preferably the ethylene-1-butene polymer component (Y), to the MFR2 (190 ℃, 2.16 kg, ISO1133) of the final multimodal metallocene-catalyzed linear low density polyethylene (mLLDPE-2) is at least 100 to 600, preferably 200 to 500, and more preferably 300 to 400.

11. The multilayer polyethylene film according to any one of claims 1 to 10, wherein The film has a hot tack force (maximum hot tack force) of at least 5.8 N or more as measured on a three-layer blown film sample (thickness 60 μm) according to ASTM F1921-98 (2004) Method B, preferably, the hot tack force (HTF) is in the range of 5.8 N to 15.0 N, more preferably in the range of 6.6 to 12.0 N, even more preferably in the range of 7.5 to 10.0 N.

12. The multilayer polyethylene film according to any one of claims 1 to 11, having at least the following characteristics a) a hot tack force (maximum hot tack force (HTF)) measured on a three-layer blown film sample (thickness 60 μm) according to ASTM F 1921-98 (2004) Method B is in the range of 5.8 N to 15.0 N, more preferably in the range of 6.6 to 12.0 N, even more preferably in the range of 7.5 to 10.0 N, and b) a hot stick temperature (HTT) measured on a three-layer blown film sample (thickness 60 μm) according to ASTM F 1921-98 Method B is lower than 90°C, and is in the range of 65 to 86°C, more preferably in the range of 68 to 85°C, and more preferably in the range of 70 to 82°C; and c) The haze measured on a 60 μm three-layer test blown film according to ASTM D1003 is in the range of 5% to 48%, more preferably 10% to 45%, even more preferably 15% to 41% or less.

13. The multilayer polyethylene film according to any one of claims 1 to 12, wherein The film satisfies the inequality (I) (SIT+HTT) / HTF<23, preferably <22, and more preferably <21, wherein SIT is the seal initiation temperature determined on a three-layer blown film with a thickness of 60 μm as described in the experimental part, HTT is the hot tack temperature measured on a three-layer test blown film sample with a thickness of 60 μm according to ASTM F 1921-98 Method B, and HTF is the hot tack force measured on a three-layer test blown film sample with a thickness of 60 μm according to ASTM F 1921-98 (2004) Method B.

14. The multilayer polyethylene film according to any one of the preceding claims, characterized in that The thickness of the skin layer (SKL) of the multilayer polyethylene film is in the range of 1 to 100 μm, preferably in the range of 5 to 80 μm, more preferably in the range of 10 to 15 μm; and / or The optional core layer (CL) of the multilayer polyethylene film has a thickness in the range of 10 to 200 μm, preferably in the range of 20 to 80 μm, more preferably in the range of 30 to 45 μm; and / or The thickness of the sealing layer (SL) of the multilayer polyethylene film is in the range of 1 to 50 μm, preferably in the range of 5 to 25 μm, more preferably in the range of 10 to 15 μm; and / or The thickness of the multilayer polyethylene film is in the range of 12 to 350 μm, preferably in the range of 40 to 150 μm, and more preferably in the range of 80 to 90 μm.

15. Use of the film according to any one of the preceding claims 1 to 14 as packaging material, in particular as packaging material for food and / or medical products.

Citation Information

Patent Citations

  • Laminated film structure based on polyethylene only

    CN107428138A

  • Multilayer polymer film

    CN111315567A

  • Polypropylene composition with improved sealing behaviour

    IN202017030208A

  • Multilayer laminate film assembly and standing pouch

    US20190022988A1

  • C2C3 Random Copolymer Composition

    US20210214478A1